Biodegradable compositions and methods of manufacture

By adding filler materials to the biodegradable composition, adjusting its C:N ratio and extractable micronutrient concentration, the problem that biodegradable polymers in the prior art are difficult to biodegradable under non-industrial composting conditions is solved, and the effect of rapid biodegradation and wide application is achieved.

CN119677805APending Publication Date: 2025-03-21COMPOST CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380053031.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-10
Filing Date
2023-06-01
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing biodegradable polymers are difficult to effectively biodegradable under non-industrial composting conditions, and their application is limited by industrial composting conditions.

Method used

By adding filler materials to the biodegradable composition, the carbon-nitrogen ratio (C:N ratio) and the concentration of extractable micronutrients are adjusted, and the biodegradability rate under non-industrial composting conditions is significantly improved.

Benefits of technology

Rapid biodegradation under non-industrial composting conditions is achieved, the dependence on industrial composting conditions is reduced, and a wider application possibility is provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005236416840000271
    Figure BDA0005236416840000271
  • Figure BDA0005236416840000281
    Figure BDA0005236416840000281
  • Figure BDA0005236416840000282
    Figure BDA0005236416840000282
Patent Text Reader

Abstract

The invention relates to a biodegradable composition as well as a preparation method and application thereof. The invention also relates to an additive for enhancing the biodegradation of the composition. The invention also relates to a method for modulating the biodegradability of a composition.
Need to check novelty before this filing date? Find Prior Art

Description

Field of the Invention

[0001] The present invention relates to a biodegradable composition and a method for preparing and using the composition. The present invention also relates to an additive for enhancing the biodegradability of the composition. The present invention also relates to a method for regulating the biodegradability of the composition. Background Art

[0002] Plastic waste accumulation is a recognized problem that has yet to be satisfactorily resolved. A large amount of this waste comes from petrochemical products. While a certain degree of product life is usually expected, this may be as little as a few minutes for a single use, and it is estimated that commonly used polymers such as polyethylene, polyethylene terephthalate (PET) and polystyrene can last up to 500 to 5,000 years.

[0003] Since the 1980s, biodegradable polymers have been gaining popularity and being used to replace some non-biodegradable materials. Some of the challenges that have not been satisfactorily addressed by such biodegradable polymers are:

[0004] They often require industrial composting systems to “biodegrade”, and these extreme conditions are not accessible to consumers everywhere. This means that the biodegradable polymers consumed in these places are often only slightly better than traditional plastics; and / or

[0005] They often only partially break down into microplastics which are not themselves biodegradable.

[0006] For these reasons, polylactic acid (PLA) is not considered biodegradable under some certification schemes (US and European standards) because it does not biodegrade outside of artificial composting conditions.

[0007] Some so-called "home compostable plastics" have been developed that meet standards set by certain countries, but their application is limited and these standards are not universally accepted.

[0008] Some biodegradable polymers are also biobased polymers, which means they are made entirely or in part from biomass such as plants, algae, bacteria or other microorganisms. This biomass is generally considered a renewable resource.

[0009] It is an object of the present invention to provide a biodegradable composition which does not require industrial composting conditions.Ideally, the biodegradable composition can be used to form a range of products designed to desired specifications.

[0010] Alternatively or additionally, it may be an object of the invention to provide the public with a useful choice. Summary of the invention

[0011] existFirst In one aspect, the present invention provides a biodegradable composition comprising a polymer and a filler such that the composition has a C:N ratio of 15 to 200, such as 30 to 200. Typically, the composition will have a C:N ratio of 15 to 200, such as 30 to 200, prior to exposure to composting conditions.

[0012] It has now been recognized that the biodegradation rate of the composition of the present invention under non-industrial composting conditions can be significantly increased by providing a filler material to the composition, which can be used to adjust the total carbon-nitrogen ratio (C:N ratio) of the composition. For example, the filler can provide a nitrogen source for the composition, otherwise the composition may be seriously lacking in nitrogen. Without wishing to be bound by theory, it is believed that the C:N ratio is adjusted to a specific range by using a filler, which causes biodegradation by providing a biodegradation site preferred by microorganisms. When using a filler, it is also shown that the C:N ratio will usually increase over time after being exposed to household composting conditions. This shows that over time, microbial growth consumes nitrogen in situ.

[0013] exist second In one aspect, the present invention provides a biodegradable composition comprising a polymer and a filler, such that the composition has an extractable phosphorus concentration of at least 5 mg / kg. Typically, the composition will have an extractable phosphorus concentration of at least 5 mg / kg before exposure to composting conditions.

[0014] It has now been recognized that the biodegradation rate of the composition of the present invention under non-industrial composting conditions can be significantly increased by providing a filler material to the composition, which can be used to adjust the extractable phosphorus concentration of the composition. For example, the filler can provide a phosphorus source for the composition, otherwise the composition may be seriously lacking in phosphorus. Without wishing to be bound by theory, it is believed that the extractable phosphorus concentration of the composition is increased by using a filler, which triggers biodegradation by providing a biodegradation site preferred by microorganisms. When using a filler, the extractable phosphorus concentration of the composition can increase over time after being exposed to home composting conditions. This shows that over time, microbial growth can promote the in-situ release of phosphorus, and / or microbial growth can promote the decomposition of the composition in the soil environment.

[0015] exist third In one aspect, the present invention provides a biodegradable composition comprising a polymer and a filler, such that the composition has an extractable potassium concentration of at least 10 mg / kg.

[0016] It has now been recognized that the biodegradation rate of the composition of the present invention under non-industrial composting conditions can be significantly increased by providing filler materials to the composition, which can be used to adjust the extractable potassium concentration of the composition. For example, the filler can provide a potassium source for the composition, otherwise the composition may be seriously lacking in potassium. Without wishing to be bound by theory, it is believed that the extractable potassium concentration of the composition is increased by using fillers, which trigger biodegradation by providing biodegradation sites preferred by microorganisms. When fillers are used, the extractable potassium concentration of the composition can increase over time after being exposed to home composting conditions. This shows that over time, microbial growth can promote the in situ release of phosphorus, and / or microbial growth can promote the decomposition of the composition in the soil environment.

[0017] exist fourth In one aspect, the present invention provides a biodegradable composition comprising a polymer and a filler, so that the composition has:

[0018] a C:N ratio of 15 to 200, such as 30 to 200; and

[0019] An extractable phosphorus concentration of at least 5 mg / kg; and / or

[0020] Extractable potassium concentration of at least 10 mg / kg.

[0021] exist fifth In one aspect, the present invention provides a biodegradable composition comprising a polymer and a filler, so that the composition has:

[0022] a C:N ratio of 15 to 200, such as 30 to 200; and

[0023] An extractable phosphorus concentration of at least 5 mg / kg; and

[0024] Extractable potassium concentration of at least 10 mg / kg.

[0025] exist sixth In one aspect, the present invention provides a biodegradable composition comprising a polymer and a filler, so that the composition has:

[0026] An extractable calcium concentration of at least 15 mg / kg; and / or

[0027] An extractable magnesium concentration of at least 1 mg / kg; and / or

[0028] An extractable sodium concentration of at least 15 mg / kg; and / or

[0029] An extractable manganese concentration of at least 0.05 mg / kg; and / or

[0030] An extractable iron concentration of at least 0.05 mg / kg; and / or

[0031] An extractable aluminium concentration of at least 0.05 mg / kg; and / or

[0032] An extractable zinc concentration of at least 0.05 mg / kg; and / or

[0033] An extractable copper concentration of at least 0.1 mg / kg; and / or

[0034] · Extractable boron concentration of at least 0.1 mg / kg.

[0035] It has now been recognized that the biodegradation rate of the composition of the present invention under non-industrial composting conditions can be significantly increased by providing filler materials to the composition, and the filler materials can be used to adjust the concentration of (one or more) extractable micronutrients of the composition. For example, the filler can provide the composition with (one or more) micronutrient sources listed above, otherwise the composition may be seriously lacking in the (one or more) micronutrients. Without wishing to be bound by theory, it is believed that the (one or more) extractable micronutrient concentration of the composition is increased by using fillers, and the filler causes biodegradation by providing a biodegradation site preferred by microorganisms. When using fillers, the (one or more) extractable micronutrient concentration of the composition can increase over time after being exposed to household composting conditions. This shows that over time, microbial growth can promote the in-situ release of (one or more) micronutrients, and / or microbial growth can promote the decomposition of the composition in the soil environment.

[0036] exist seventh In one aspect, the present invention provides a biodegradable composition comprising a polymer and a filler, so that the composition has:

[0037] a C:N ratio of 15 to 200, such as 30 to 200; and

[0038] An extractable phosphorus concentration of at least 5 mg / kg; and / or

[0039] An extractable potassium concentration of at least 10 mg / kg; and / or

[0040] An extractable calcium concentration of at least 15 mg / kg; and / or

[0041] An extractable magnesium concentration of at least 1 mg / kg; and / or

[0042] An extractable sodium concentration of at least 15 mg / kg; and / or

[0043] An extractable manganese concentration of at least 0.05 mg / kg; and / or

[0044] An extractable iron concentration of at least 0.05 mg / kg; and / or

[0045] An extractable aluminium concentration of at least 0.05 mg / kg; and / or

[0046] An extractable zinc concentration of at least 0.05 mg / kg; and / or

[0047] An extractable copper concentration of at least 0.1 mg / kg; and / or

[0048] · Extractable boron concentration of at least 0.1 mg / kg.

[0049] The present invention also provides a filler that can be used to adjust the properties of a polymer to enhance biodegradation.

[0050] exist eighth In one aspect, the present invention provides a filler for incorporation into a biodegradable composition, the filler providing a source of at least one of: nitrogen; phosphorus; potassium; calcium; magnesium; sodium; manganese; iron; aluminum; zinc; copper; and boron, such that the biodegradable composition incorporating the filler has:

[0051] A C:N ratio of 15 to 200, such as 30 to 200; and / or

[0052] An extractable phosphorus concentration of at least 5 mg / kg; and / or

[0053] An extractable potassium concentration of at least 10 mg / kg; and / or

[0054] An extractable calcium concentration of at least 15 mg / kg; and / or

[0055] An extractable magnesium concentration of at least 1 mg / kg; and / or

[0056] An extractable sodium concentration of at least 15 mg / kg; and / or

[0057] An extractable manganese concentration of at least 0.05 mg / kg; and / or

[0058] An extractable iron concentration of at least 0.05 mg / kg; and / or

[0059] An extractable aluminium concentration of at least 0.05 mg / kg; and / or

[0060] An extractable zinc concentration of at least 0.05 mg / kg; and / or

[0061] An extractable copper concentration of at least 0.1 mg / kg; and / or

[0062] · Extractable boron concentration of at least 0.1 mg / kg.

[0063] exist ninth In one aspect, the present invention provides a method for increasing the biodegradation rate of a composition, comprising mixing (such as blending) a filler and a polymer so that the composition has:

[0064] A C:N ratio of 15 to 200, such as 30 to 200; and / or

[0065] An extractable phosphorus concentration of at least 5 mg / kg; and / or

[0066] An extractable potassium concentration of at least 10 mg / kg; and / or

[0067] An extractable calcium concentration of at least 15 mg / kg; and / or

[0068] An extractable magnesium concentration of at least 1 mg / kg; and / or

[0069] An extractable sodium concentration of at least 15 mg / kg; and / or

[0070] An extractable manganese concentration of at least 0.05 mg / kg; and / or

[0071] An extractable iron concentration of at least 0.05 mg / kg; and / or

[0072] An extractable aluminium concentration of at least 0.05 mg / kg; and / or

[0073] An extractable zinc concentration of at least 0.05 mg / kg; and / or

[0074] An extractable copper concentration of at least 0.1 mg / kg; and / or

[0075] · Extractable boron concentration of at least 0.1 mg / kg.

[0076] It should be understood that the C:N ratio of the polymer; and / or the concentration of the various elements outlined in the ninth aspect in the polymer may be known before the filler is mixed (such as blended) into the composition. In this case, the technician will accurately select a filler with the desired chemical composition to achieve the value. Otherwise, where the C:N ratio of the polymer; and / or the concentration of the various elements outlined in the ninth aspect in the polymer is unknown before the filler is mixed (such as blended) into the composition, standard methods (further detailed below) can be used to calculate these values. From this point of view, the technician will accurately select a filler with the desired chemical composition to achieve the value.

[0077] In some embodiments, the step of mixing (such as blending) the filler and the polymer will include a step of thermoforming or injection molding. BRIEF DESCRIPTION OF THE DRAWINGS

[0078] One or more embodiments of the present invention will be described below by way of example only and not by way of limitation, with reference to the following drawings, in which:

[0079] Figure 1 is a front view of a plant container according to one embodiment of the present invention.

[0080] Figure 2 is a bottom view of a plant container according to one embodiment of the present invention.

[0081] Figure 3 is a cross-sectional view of a plant container according to one embodiment of the present invention.

[0082] Figure 4 Yes Figure 1 Exploded view of section "B" shown.

[0083] Figure 5 is a front view of a unit of a tray of a single plant container according to one embodiment of the present invention.

[0084] Figure 6 Yes Figure 5 Exploded view of section "B" shown.

[0085] Figure 7 This is a photograph of the plant container "A" used in the 60th day above-ground degradation test.

[0086] Figure 8 This is a photograph of the plant container "A" used in the 60th day above-ground degradation test.

[0087] Fig. 9 This is a photograph of plant container "B" used in the 60th day above-ground degradation test.

[0088] Fig.10 is a photograph of the plant container "A" used in the below ground degradation test after approximately 7 weeks.

[0089] Fig.11 is a photograph of the plant container "A" used in the below ground degradation test after approximately 7 weeks.

[0090] Fig.12 is a photograph of plant container "B" used in the below ground degradation test after approximately 7 weeks.

[0091] Fig.13 is a photograph of plant container "B" used in the below ground degradation test after approximately 7 weeks.

[0092] Fig.14is a scanning electron microscope (SEM) image of sample ID#1 (thermoformed PBS / PLA composite without filler), which shows a smooth surface and a uniform interior.

[0093] Fig.15 This is a scanning electron microscope (SEM) image of sample ID#2 (thermoformed starch composite). Starch granules are easily seen on the surface and inside.

[0094] Fig.16 is a scanning electron microscope (SEM) image of sample ID#3 (thermoformed blood & bone composite). Large particles of varying sizes are seen in the voids within the matrix.

[0095] Fig.17 is a scanning electron microscope (SEM) image of sample ID#7 (thermoformed fish meal composite). Larger particles of varying sizes are seen in the voids within the matrix.

[0096] Fig.18 is a scanning electron microscope (SEM) image of sample ID#12 (thermoformed blood & bone composite) showing cracking after 4 months of soil exposure.

[0097] Fig.19 is a scanning electron microscope (SEM) image of sample ID#13 (thermoformed blood & bone composite) showing cracking after 6 months of soil exposure.

[0098] Fig. 20 is a scanning electron microscope (SEM) image of sample ID#21 (injection molded blood & bone composite) showing a uniform surface after 6 months of soil exposure.

[0099] Fig.21 is a scanning electron microscope (SEM) image of sample ID #22 (injection molded starch composite) showing small pores after 6 months of soil exposure.

[0100] Fig. 22 is a scanning electron microscope (SEM) image of sample ID #23 (injection molded fish meal composite) showing cracking after 6 months of soil exposure.

[0101] Figure 23-36 are photographs of samples of various compositions showing the extent of biodegradation under domestic soil conditions. DETAILED DESCRIPTION

[0102] As used herein, the term "biodegradable composition" refers to a composition that is biodegradable at least under non-industrial composting conditions, but may also be biodegradable under industrial composting conditions.

[0103] As described herein, many so-called "biodegradable polymers" are only biodegradable under very specific conditions that are not ubiquitous. Many geographic centers do not have access to industrial composting conditions, which means that such "biodegradable polymers" essentially never biodegrade within a reasonable period of time, resulting in landfill waste. Even when such industrial composting facilities are available in geographic centers, consumer preferences (usually laziness) or lack of widespread collection points mean that such biodegradable polymers end up in landfills, again never biodegrading within a reasonable period of time. In some cases, industrial composting facilities may be prohibited from recycling bio-based polymers (such as PLA) because restrictive local regulations / bylaws may (for example) stipulate that the facility can only accept green matter.

[0104] Therefore, it is desirable to provide biodegradable compositions that are capable of biodegrading under non-industrial conditions, such as home composting, in soil or even as part of a landfill. The biodegradable compositions of the present invention meet this need, or at least to some extent, such as to a large extent.

[0105] As used herein, the expression "industrial" in relation to composting conditions refers to those conditions which typically involve temperatures between 50°C and 60°C. Typically, industrial composting conditions will be aerobic, rather than anaerobic. Industrial composting conditions typically involve two distinct phases: (i) active composting; followed by (ii) curing. The active composting phase may include a minimum period of 21 days, during which temperatures may reach 50°C to 60°C, while during the curing phase, the decomposition rate decreases and the temperature drops to <40°C. During these phases, process parameters such as material structure (particle size), mixing, relative humidity, temperature, pH, and carbon / nitrogen ratio may be controlled.

[0106] Such industrial composting conditions are detailed in the following standards (incorporated herein by reference):

[0107] Europe - EN13432 - "Requirements for packaging that is recyclable by composting and biodegradation". This test requires compostable plastics to disintegrate after 12 weeks (at least 90% of the product should be able to pass through a 2 x 2mm sieve) and to be fully biodegradable after six months (at least 90% of the organic material is converted into CO2). The test is conducted at 58°C.

[0108] USA-ASTM D6400 - "Standard Specification for Labeling Plastics Intended for Aerobic Composting in Municipal or Industrial Facilities". This test covers plastics and products made from plastics designed for composting in municipal and industrial aerobic facilities. This test is conducted at 58°C.

[0109] Australia - AS4736 - Biodegradable plastics suitable for composting and other microbiological treatments.

[0110] As used herein, the expression "non-industrial" in relation to composting conditions refers to substantially all conditions that are not included in the industrial composting conditions described herein. Such conditions are generally considered to be "milder" and are characterized by operating at temperatures much lower than 50-60°C. In general, such conditions will not include conditions that preserve the biodegradable composition during its functional life. For example, when the biodegradable composition is to be used to form a container, it is preferred that the biodegradable composition is substantially non-biodegradable when it is used as a container. In general, non-industrial composting conditions refer to conditions to which the biodegradable composition is exposed after the end of its functional life, usually by a conscious decision by the user to compost the product, i.e., to place the biodegradable composition in the waste stream. This step typically involves contacting the biodegradable composition with other waste products, although it is conceivable that the biodegradable composition is left alone. In one embodiment, non-industrial composting conditions may include burying in the ground, although such conditions are preferably aerobic.

[0111] Specific examples of non-industrial composting conditions are those associated with:

[0112] "Home composting conditions" - Such conditions involve biodegradation at or slightly above ambient temperature, and usually under aerobic conditions. Such conditions are commonly used to process organic wastes, especially garden wastes. Unlike industrial composting, such biodegradation usually occurs under uncontrolled conditions. Standards for testing biodegradation under home composting conditions have been developed and include (each of which is incorporated herein by reference):

[0113] o International - ISO 14855-1 (2012) - The test is conducted under aerobic conditions at 25°C.

[0114] This test methodology is used in the examples to support the present invention;

[0115] o Australia - AS5810 - Biodegradable plastics suitable for home composting. This test is conducted at 25°C + / - 5°C;

[0116] o France - NF T 51800;

[0117] oAustria - prEN 17427-TUV

[0118] "Soil Biodegradability Conditions" - a standard has been developed (which is incorporated herein by reference) to specifically test biodegradation in soil;

[0119] o Europe - EN 17033 - Biodegradable mulches for agricultural and horticultural use; and

[0120] "Landfill" Biodegradation Conditions - A standard has been developed (which is incorporated herein by reference) to specifically test biodegradation in landfills:

[0121] o ASTM D5526 - Standard Test Method for Determining the Anaerobic Biodegradation of Plastic Materials under Accelerated Landfill Conditions. This test is conducted at approximately 35°C.

[0122] The biodegradable compositions of the present invention are generally biodegradable under at least one standard set forth herein or defined elsewhere for non-industrial composting. Preferably, the biodegradable compositions of the present invention are biodegradable at least under ISO 14855-1 (2012). It should be understood that, although poly(butylene succinate) (PBS) is biodegradable under non-industrial composting conditions, polylactic acid (PLA) is not, and neither is the combination of the two, i.e., under at least one standard set forth herein or defined elsewhere for non-industrial composting, compositions comprising PLA are not considered to be capable of significant biodegradation. In particular, it is understood that, according to ISO 14855-1 (2012), PLA itself or in combination with PBS is not considered to be capable of biodegradation. Those skilled in the art will appreciate that PLA degrades most effectively at a temperature of about 55-60°C.

[0123] Preferably, the biodegradable composition of the present invention is configured to undergo appreciable biodegradation within 12 months of exposure to non-industrial composting conditions. Preferably, the biodegradable composition of the present invention is configured to undergo appreciable biodegradation within 6-12 months of exposure to non-industrial composting conditions.

[0124] Preferably, the biodegradable composition of the present invention is configured to completely biodegrade within 24 months when exposed to non-industrial composting conditions. More preferably, the biodegradable composition of the present invention is configured to completely biodegrade within 18-24 months when exposed to non-industrial composting conditions.

[0125] In a preferred embodiment, the biodegradable compositions of the present invention have been shown to undergo at least 60% biodegradation within 60 days of exposure to non-industrial composting conditions. In a preferred embodiment, the biodegradable compositions of the present invention have been shown to undergo about 80% biodegradation within 190 days of exposure to non-industrial composting conditions. In these same studies, the positive control composition made of cellulose degraded by about 82%, and therefore the preferred embodiments of the biodegradable compositions of the present invention were calculated to have a relative biodegradation of over 95%. In contrast, the combination of PBS and PLA without fillers has been shown to biodegrade only about 10% within a similar time frame.

[0126] Such biodegradation rate makes the biodegradable composition of the present invention particularly suitable for those applications where the functional life of the product is relatively short, such as take-out containers, food trays, beverage cups, etc. That is, without wishing to be bound by theory, it is believed that the biodegradation rate can be adjusted by increasing or reducing the amount of filler and / or the chemical characteristics of the filler. Without wishing to be bound by theory, it is believed that the filler can cause biodegradation by providing a nutrient source to the microorganism responsible for biodegradation. Scanning electron microscopy (SEM) shows that for some fillers, there is a space / void between the filler and the polymer. The space / void can also serve as a reservoir for microbial growth and / or nutrient leaching from the filler to the surrounding area. Therefore, the easier it is to obtain nutrition (such as when it is provided in an increased amount, with a high surface area: volume ratio, such as provided in a small particle size, located on the outer surface, etc.), the higher the rate of biodegradation may be. On the contrary, when nutrition is less likely to be obtained (such as when it is provided in a reduced amount, with a low surface area: volume ratio, such as provided in a large particle size, located inside the composition, etc.), the lower the rate of biodegradation may be. Advantageously, the fillers of the present invention provide the user with the ability to configure the biodegradable composition to provide a desired biodegradation rate.

[0127] In one application, the biodegradable composition of the present invention is used to form a container suitable for growing plants therein. Typically, the growing season of plants above ground lasts up to about 12 months, depending on the growth of plant matter. In some forms, the biodegradable container formed from the biodegradable composition of the present invention can be configured to ensure that it does not degrade to a significant degree before the container may be ready for planting. Such containers can be planted in situ where it is intended that the plants continue to grow.

[0128] The fillers included in the biodegradable composition of the present invention can be used to impart mechanical stiffness to the biodegradable composition for a certain period of time and under certain conditions (such as during the functional life of the biodegradable composition), so that after it is exposed to non-industrial composting conditions, the mechanical stiffness decreases, which in turn can promote accelerated biodegradation.

[0129] For example, in above-ground degradation tests, plant containers made from the biodegradable composition of the present invention were shown to maintain good mechanical stability and integrity during the growth of the plant. It is believed that the use of fillers provides this advantage to the container. It is also envisioned that the use of fillers in the composition will also provide nutrients to the soil when the container degrades in the soil. It was also unexpectedly found that fillers greatly enhanced the degradation of the composition.

[0130] As used herein, the term "polymer" forming the part of biodegradable composition refers to any polymeric material that can biodegrade under industrial or non-industrial composting conditions. Advantageously, filler of the present invention is mixed in the biodegradable composition of the present invention to increase the rate of biodegradation, so that the polymer that may be considered to be unsatisfactorily biodegradable under non-industrial composting conditions can form a biodegradable composition that can biodegrade under non-industrial composting conditions. As a non-limiting example, pure polylactic acid (PLA) can be generally considered to show poor biodegradation under non-industrial composting conditions, but when combined with filler of the present invention, the composition so formed shows a satisfactory biodegradation rate under non-industrial composting conditions.

[0131] Typical decomposition products of such polymers may include: naturally occurring gases (such as carbon dioxide and nitrogen); water; biomass (such as one or more components used to form the polymer from natural sources, such as polysaccharides); smaller subunits derived from microorganisms or synthesis (such as alcohol acids); and salts. Typically, such polymers have a large number of cleavable functional groups, such as esters, amides, urethanes and / or ethers. Such cleavable functional groups are generally cleavable by hydrolysis and / or microbial action.

[0132] Examples of polymers suitable for use in the present invention include agricultural polymers and synthetic polymers. As used herein, "agricultural polymers" refer to naturally occurring polymers, or polymers derived from naturally occurring polymers. As used herein, "synthetic polymers" may include polymers produced entirely synthetically, and may also include polymers produced at least in part by natural processes such as fermentation (such as microbial fermentation). For example, polylactic acid (PLA) can be formed by (synthetic) polymerization of monomers derived from fermentation of plant starch.

[0133] Examples of agricultural polymers include: proteins (such as silk, wool, collagen); polysaccharides (such as starch, cellulose, chitin, chitosan, alginic acid, cellophane); polypeptides (such as gelatin, wheat gluten, casein, whey protein).

[0134] Examples of synthetic polymers include:

[0135] Aliphatic polyesters, such as:

[0136] Polyglycolide / poly(glycolic acid) (PGA)

[0137] Polycaprolactone (PCL)

[0138] Polydioxanone (PDO)

[0139] Polylactic acid (PLA) (including poly (L-lactic acid), poly (D-lactic acid) and poly (DL-lactic acid))

[0140] Poly(lactic-co-glycolic acid) (PLGA)

[0141] Poly(trimethylene carbonate) (PTMC)

[0142] Poly(alkyl succinates), this family includes:

[0143] (i) Poly(ethylene succinate) (PES)

[0144] (ii) Poly(propylene succinate) (PPS)

[0145] (iii) Poly(butylene succinate) (PBS)

[0146] (iv) Poly(butylene succinate-co-butylene adipate) (PBSA) is a biodegradable semi-crystalline polyester prepared by the co-condensation of succinic and adipic acids with 1-4-butanediol.

[0147] Polyhydroxyalkanoates (PHA), this family includes:

[0148] (i) Polyhydroxybutyrate (PHB)

[0149] (ii) Polyhydroxyvalerate (PHV)

[0150] (iii) Polyhydroxycaproate (PHH)

[0151] (iv) Polyhydroxyoctanoate (PHO)

[0152] (v) Polyhydroxydecanoate (PHD)

[0153] (vi) Polyhydroxy-5-phenylvalerate (PHPV)

[0154] (vii) Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV)

[0155] Aromatic polyesters, such as poly(butylene adipate-co-terephthalate) (PBAT);

[0156] Polyamides, such as BAK 1095 and BAK 2195 (based on caprolactam, butanediol and adipic acid;

[0157] Polyurethanes, which typically include a biodegradable portion consisting of polyesters (such as PCL, PLA and PGA), agropolymers (such as chitin); and

[0158] - Vinyl alcohols, such as polyvinyl alcohol and poly(vinyl acetate). Such polymers are generally susceptible to oxidation and / or microbial degradation.

[0159] In some embodiments where PHB is used, a polymer selected from the group consisting of: PLA; PBAT; PHBV; PCL; PBS is also used. Typically, where PHB is used, it is used as a minor component of another polymer selected from the group consisting of: PLA; PBAT; PHBV; PCL; PBS. Preferably, PHB is not used.

[0160] Preferably, the polymer will be a synthetic polymer. More preferably, the polymer will be a polyester. Preferably, the polymer will be selected from polybutylene succinate (PBS), polylactic acid (PLA), polyhydroxyalkanoates (PHA) (such as poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV)), poly (butylene succinate-co-butylene adipate) (PBSA) and / or combinations thereof.

[0161] PBS is a thermoplastic polymer resin of the polyester family. PBS is a biodegradable aliphatic polyester with properties comparable to polypropylene. PBS is a relatively soft material and naturally decomposes into water and CO2, and is a suitable material for the biodegradable composition of the present invention. However, in processing / handling, and especially during preparation when used alone, the material is soft and may cause problems.

[0162] PLA is a thermoplastic polyester and is made primarily from renewable resources. In contrast to other thermoplastics that are petroleum-based, some of the raw materials used for PLA production include corn starch, cassava root, or sugar cane. PLA is bio-based and biodegradable, but usually only under industrial composting conditions. Without industrial composting conditions, it can take 100 to 1,000 years to decompose.

[0163] As used herein, the "type" of a polymer refers to the chemical composition of the polymer backbone - eg, an agropolymer, a polyester, a polyamide, etc.

[0164] That is, it should be understood that a polymer can be characterized in many different ways, not just by the chemical composition of the polymer backbone (such as, for example, whether it is a polyester or a polyamide). For example, a polymeric material can be characterized by its degree of polydispersity (commonly expressed as PD or PDI); its average molecular weight (which itself can be provided as a number average molecular weight (M); and its molecular weight. n ); weight average molecular weight (M w ); Z average molecular weight (M z )); degree of polymerization (usually expressed as n); its degree of branching; its glass transition temperature (Tg). At least some of these values ​​can be obtained using techniques such as gel permeation chromatography (GPC) and thermogravimetric analysis (TGA), and the use of these techniques is within the skill of the skilled artisan. Regardless of the manner in which these values ​​are obtained, the present invention contemplates that polymers having all of these values ​​can be used in the biodegradable compositions and methods of the present invention.

[0165] Although the present invention contemplates the use of a single type of polymer in a biodegradable composition, it is preferred that the biodegradable composition will include multiple types of polymers. For example: a biodegradable composition may include two types of polymers; a biodegradable composition may include three types of polymers.

[0166] Advantageously, multiple polymers may be included for a variety of reasons, including providing the biodegradable composition with desired mechanical properties suitable for the intended use. The skilled artisan will appreciate that polymers each have a wide range of mechanical properties, and when combined, such as in a composite material (such as a bilayer, multilayer, or structural variant in which multiple polymers may remain partially separated), or in a mixture (such as a blend), the mechanical properties of the combination may change, including that they may change significantly. The present invention contemplates such combinations.

[0167] Without wishing to be bound by theory, it is believed that the combination of a blend of polymers (such as PLA and PBS) and fillers provides an advantage that the composition has improved mechanical properties such as stiffness and strength. In general, it is believed that PLA alone is a brittle material. Fillers such as fillers of the type described herein are included in polymer blends of PLA and PBS to unexpectedly produce compositions with improved mechanical strength and stiffness. Fillers of the type described herein can contribute to the stiffness of the product made from the biodegradable composition, but may slightly reduce strength (e.g., tensile strength, impact strength). It is believed that the use of PBS is to increase strength. In addition, in conjunction with improved biodegradability, it should be understood that the biodegradable composition of the present invention makes it very suitable for a variety of different applications. The characteristics of the biodegradable composition can be changed as needed by changing the components and the ratio of these components. For example, the amount of PLA in the composition can be increased as needed to produce greater stiffness in the final composition. Increasing the stiffness of the composition will result in a harder (although possibly more brittle) product and allow further control of the degradation time of the biodegradable composition. In addition, the amount of filler can be changed to adjust the desired modulus of the biodegradable composition for processing. It can also be used to control the amount of nutrient(s) provided to the soil after degradation of the biodegradable composition.

[0168] If present, multiple polymers may be present in any ratio. When two types of polymers are used, the polymers may be present in a ratio ranging from 1:1000 to 1000:1; such as a ratio ranging from 1:100 to 100:1; such as a ratio ranging from 1:10 to 10:1; such as a ratio ranging from 1:5 to 5:1; such as a ratio ranging from 1:3 to 3:1; such as a ratio ranging from 1:2 to 2:1. When two types of polymers are used, the polymers may be present in a ratio of about 2:1.

[0169] Preferably, the biodegradable composition will include multiple types of polymers (such as two types of polymers) selected from the group consisting of polybutylene succinate (PBS), polylactic acid (PLA), polyhydroxyalkanoates (PHA) (such as polyhydroxyalkanoates (PHB), poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV)) and / or combinations thereof. Most preferably, the biodegradable composition will include polybutylene succinate (PBS) and polylactic acid (PLA).

[0170] When the biodegradable composition includes polybutylene succinate (PBS) and polylactic acid (PLA), the polymers may be present in a ratio (PBS:PLA) ranging from 1:1000 to 1000:1; such as a ratio ranging from 1:100 to 100:1; such as a ratio ranging from 1:10 to 10:1; such as a ratio ranging from 1:5 to 5:1; such as a ratio ranging from 1:3 to 3:1; such as a ratio ranging from 1:2 to 3:1, such as a ratio ranging from 2.5:1 to 1.5:1, such as a ratio of about 2:1.

[0171] Examples of polymers that can be used in the biodegradable composition of the present invention with fillers so that the composition has a C:N ratio of 30 to 200 include:

[0172] PLA;

[0173] PBAT / PLA;

[0174] PHBV / PLA

[0175] PCL / PLA;

[0176] PBS / PLA.

[0177] For the polymer of the described or each type used in the biodegradable composition, a single grade of polymer can be used. As used herein, the term "grade" associated with polymers generally refers to a polymer that is commercially available and sold with a set of determined features such as mean molecular weight, polydispersity, etc. For example, a PLA with a mean molecular weight of 100 kDa can be used. However, this PLA grade can be blended with another PLA grade that may have a higher or lower mean molecular weight, so that the polymer blend formed in this way can have a characteristic (such a mixture can have a bimodal or multimodal molecular weight distribution) that is different from one or both of the grades of the PLA that forms it. The present invention contemplates all these grades and / or types of combinations.

[0178] The amount of polymer in the biodegradable composition of the present invention should not be considered limiting.

[0179] The concentration of the polymer may be selected so as to achieve a desired C:N ratio of the biodegradable composition; and / or the concentration of the various elements so desired and mentioned herein in the polymer. Therefore, the concentration of the polymer should not be considered limiting. It may be convenient to provide the concentration of the polymer as a percentage of the total biodegradable composition (% w / w) on a weight-to-weight basis. In some embodiments, the polymer (including multiple polymers) may be present at up to 99.99% w / w, such as up to 99% w / w, such as up to 98% w / w, such as up to 97% w / w, such as up to 96% w / w, such as up to 95% w / w, such as up to 94% w / w, such as up to 93% w / w, such as up to 92% w / w, such as up to 91% w / w, such as up to 90% w / w, such as up to 89% w / w, such as up to 88% w / w, such as up to 87% w / w, such as up to 86% w / w, such as up to 85% w / w, such as up to 80% w / w, such as up to 75% w / w, such as up to 70% w / w, such as up to 65% w / w, such as up to 60% w / w, such as up to 55% w / w, such as up to 50% w / w. In some embodiments, the polymer is present in a concentration of at least 10% w / w, such as at least 15% w / w, such as at least 20% w / w, such as at least 25% w / w, such as at least 30% w / w, such as at least 35% w / w, such as at least 40% w / w, such as at least 45% w / w, such as at least 50% w / w, such as at least 55% w / w, such as at least 60% w / w, such as at least 65% w / w, such as at least 70% w / w, such as at least 75% w / w, such as at least 80% w / w, such as at least 85% w / w, such as at least 87% w / w, such as at least 89% w / w, such as at least 90% w / w. In some embodiments, the polymer is present in a concentration of about 90% w / w, such as a concentration of 90% w / w.

[0180] Preferably, the biodegradable composition includes PBS. When present, the amount of PBS included can be 20 to 99.99% w / w of the composition, such as 20 to 95% w / w, such as 20 to 80% w / w, such as 20 to 75% w / w of the composition, such as 30 to 75% w / w, such as 40 to 75% w / w, such as 45 to 65% w / w of the composition, such as about 60% w / w, such as 60% w / w.

[0181] Preferably, the biodegradable composition includes PLA. When present, the amount of PLA included can be 10 to 99.99% w / w of the composition, such as 10 to 95% w / w, such as 10 to 80% w / w, such as 15 to 60% w / w of the composition, such as 15 to 50% w / w, such as 25 to 45% w / w, such as about 30% w / w, such as 30% w / w.

[0182] The biodegradable composition of the present invention can be used for a variety of products. The biodegradable composition of the present invention can be used to produce: pots (including plantable pots and transfer pots); dishes; feed troughs; packaging; weed barrier sheets; tubes; plates (including large shallow plates, round plates, square plates); dishes; tableware (including spoons, forks, knives, chopsticks); cups (including partial cups, cups configured for hot liquids, cold liquids); cup sleeves; cup lids; straws; bottles; bottle sleeves; bowls (including round bowls, square bowls, soup bowls); trays (including market trays, propagation trays, transfer trays, catering trays, takeaway trays, lunch trays); containers (including clamshells, food boxes, take-out bowls, and containers configured for cold dishes, hot dishes, and / or ice cream); crates (for storage or transportation, such as milk or egg crates); bags (including shopping bags, pet waste bags, produce bags, waste / trash bags, sandwich bags, trash bin liners); crop stands; stands; branch tags (including clamshells, food boxes, take-out bowls, and containers configured for cold dishes, hot dishes, and / or ice cream); tags); landscape ropes / knots; cable ties; packaging materials (including sandwich packaging materials, lunch packaging materials and can packaging materials); baskets (including basket components); shed films; and personal items such as eyeglasses (sunglasses), side pockets, handbags, yoga mats, beach mats, towels, wallets, backpacks, cell phone cases, belts, umbrellas, toothbrushes, decking, jandals, footwear, and shoe soles.

[0183] As used herein, the "filler" of the present invention is a particulate material that can be incorporated into a biodegradable composition. The filler is usually added to the polymer of the present invention and mixed with the polymer (such as blending). Usually, the filler and polymer are mixed before the polymer is formed into the desired article, but this should not be considered as limiting, and the filler can be applied to the polymer (such as its surface) after the polymer has been formed into the desired article.

[0184] In the context of the present invention, fillers are generally selected to achieve the desired C:N ratio of the biodegradable composition; and / or the concentration of the various elements so desired and mentioned herein in the biodegradable composition. Taking into account the desired function, the present invention is not limited to the use of any particular type or amount of fillers. Although the present invention contemplates the use of a single filler, in some embodiments, multiple fillers will be used. The multiple fillers can be pre-mixed before mixing with the polymer, or can be added separately. Typically, where multiple fillers are used, the fillers will be pre-mixed before mixing with the polymer. Advantageously, the use of multiple fillers enables the user to achieve the desired C:N ratio of the biodegradable composition; and / or the concentration of the various elements so desired and mentioned herein in the biodegradable composition. Without wishing to be bound by theory, fillers are suitable for enhancing the non-industrial biodegradation of biodegradable compositions.

[0185] As used herein, "C:N ratio" refers to the ratio of carbon to nitrogen in a referred object such as a biodegradable composition or polymer or filler. Typically, it refers to the carbon to nitrogen ratio of a biodegradable composition. A range of elemental analysis techniques are available to technicians to determine carbon and nitrogen content. Total nitrogen can be considered to be composed of organic nitrogen, ammonium nitrogen, nitrates and nitrites. In known solid materials, it can be assumed that nitrate and nitrite nitrogen can be ignored in some cases. Total Kjehldahl nitrogen (TKN) measures organic nitrogen and ammonium nitrogen. The Dumas method (furnace) measures total nitrogen after converting organic nitrogen, ammonium nitrogen, nitrates and nitrites into gases. There are other methods to measure nitrogen, such as total nitrogen in water, where total nitrogen can be dissolved in water after digestion. One such technique is the persulfate oxidation technique for nitrogen in water, which is performed under heated alkaline conditions, where all organic and inorganic forms of nitrogen are oxidized to nitrates. Extractable nitrogen can usually be measured as extractable ammonium.

[0186] Preferably, the biodegradable composition of the present invention will have a C:N ratio of 15 to 200, such as 30 to 200, such as 15 to 150, such as 30 to 150, such as 15 to 100, such as 30 to 100, such as 50 to 100, such as 60 to 85, such as 75 to 85, such as about 79, such as 79. Typically, before exposure to composting conditions, the composition will have a C:N ratio of 15 to 200, such as 30 to 200. In some cases, the C:N ratio of the material may increase after exposure to composting conditions.

[0187] In addition to methods for determining total and extractable nitrogen, other extractable element values ​​can be obtained using extraction methods such as Mehlich 3, which is well known and most commonly used to determine the availability of soil macronutrients (such as phosphorus, calcium, magnesium, and potassium) and soil micronutrients (such as copper, zinc, manganese, and iron).

[0188] As used herein, "extractable phosphorus" refers to phosphorus determined using a method such as Mehlich 3. Preferably, the biodegradable composition has an extractable phosphorus concentration of at least 5 mg / kg, such as at least 50 mg / kg, such as at least 75 mg / kg, such as at least 90 mg / kg. Typically, before exposure to composting conditions, the composition will have an extractable phosphorus concentration of at least 5 mg / kg. In some cases, after exposure to composting conditions, the extractable phosphorus concentration of the material may increase.

[0189] As used herein, "extractable potassium" refers to phosphorus determined using a method such as Mehlich 3. Preferably, the biodegradable composition has an extractable phosphorus concentration of at least 10 mg / kg, such as at least 20 mg / kg, such as at least 25 mg / kg, such as at least 30 mg / kg, such as at least 40 mg / kg, such as at least 50 mg / kg. Typically, before exposure to composting conditions, the composition will have an extractable potassium concentration of at least 5 mg / kg. In some cases, after exposure to composting conditions, the extractable potassium concentration of the material may increase.

[0190] Typically, the or each filler used in the biodegradable composition of the invention is substantially solid at room temperature, although in some embodiments the filler may include at least a portion which is liquid at room temperature.

[0191] Typically, the filler itself will be biodegradable. For example, the filler may be derived from an animal (such as terrestrial, atmospheric, aquatic), fungal, plant (such as terrestrial, aquatic) or inorganic source. Preferably, the filler will be a processed material rather than a raw material.

[0192] Examples of fillers that can be used in the present invention include the following:

[0193] Animal Origin - Solid

[0194] bone meal; blood meal; blood and bone; beeswax; insect meal; ground meal worms; fish meal; crab meal; whey powder; worm castings; leather powder; animal waste (including human sewage / feces, animal manure (such as chicken manure, sheep manure / pellet)); gelatin; silkworm litter; collagen; horn meal; horn scrapings; feather meal;

[0195] Animal Origin - Liquid

[0196] fish oil;

[0197] Fungal origin

[0198] mushroom powder; fungus powder;

[0199] Plant-derived solids

[0200] Cottonseed meal; ground seaweed; cork; seeds; peat; wood ash; wood flour; sawdust; wood fiber (e.g., from hardwood, softwood); fiber from grasses (including bamboo); flax; abaca; sisal; ramie; hemp; and bagasse; processed starch; cellulose; cellulose fiber; tea seed meal; cassava residue; distiller's grain; coffee grounds; rice husks (rice skin); oat hulls; shells (including ground pecan shells, ground almonds, ground walnut shells, ground almond shells, coconut shell meal); corn meal; distillers grains; sunflower seed hulls; pea flour; soy protein; canola meal; soybean meal; kiwifruit hair (which can be collected in the extractor / cyclone separator in the kiwifruit packing house); starch (although starch is generally less preferred);

[0201] Plant-derived liquid

[0202] Soybean oil; Castor oil; Vegetable oil; Sunflower oil; Coconut oil; Avocado oil; Olive oil;

[0203] Inorganic

[0204] pond scum;

[0205] Inorganic - Rich in Sodium

[0206] Sodium phosphate; Sodium nitrate; Sodium nitrite;

[0207] Inorganic - Rich in potassium

[0208] Potassium phosphate; Potassium nitrate; Potassium nitrite; Potassium sulfate; Potassium chloride; Potassium magnesium sulfate;

[0209] Inorganic - Rich in calcium

[0210] Calcium phosphate, calcium nitrate, calcium nitrite, calcium ammonium nitrate;

[0211] Inorganic - Ammonia / ammonium rich (nitrogen rich) and / or phosphorus / phosphate rich

[0212] Ammonium phosphate (diammonium phosphate, monoammonium phosphate); ammonium nitrate; ammonium chloride; ammonium sulfate; ammonium nitrate sulfate; ammonium thiosulfate;

[0213] Inorganic - magnesium rich and / or ammonia / ammonium rich (nitrogen rich) and / or phosphorus / phosphate rich

[0214] Magnesium phosphate; Magnesium nitrate; Struvite (magnesium ammonium phosphate); Wastewater mineral precipitation;

[0215] Organic - Nitrogen-rich and / or Phosphorus / Phosphate-rich

[0216] Urea; urea-ammonium nitrate, uric acid.

[0217] Without limitation, fillers may advantageously provide (secondary) functions, such as acting as a fertilizer, soil conditioner, soil enhancer, weed suppressant, and / or combinations thereof.

[0218] Advantageously, the present invention allows the technician to select a filler or a combination of fillers, such as from the list above, so as to achieve the desired C:N ratio of the biodegradable composition; and / or the concentration of various elements in the biodegradable composition so desired and mentioned herein. In some cases, the elemental composition of the polymer and / or filler will be known from the public information. In other cases, the elemental composition will be unknown, but can be derived using standard techniques known in the art. For example, total phosphorus and total potassium can be measured by digestion methods, respectively, which include dissolving the entire sample before quantitative analysis of these elements. A furnace can be used to determine total nitrogen at extremely high temperatures, but total Kjehldahl nitrogen (TKN) digestion usually provides more accurate results. Extractable nitrogen can usually be measured as extractable ammonium. Other extractable element values ​​can be obtained using extraction methods, such as Mehlich 3, which is well known and most commonly used to determine the availability of soil macronutrients (such as phosphorus, calcium, magnesium and potassium) and soil micronutrients (such as copper, zinc, manganese and iron).

[0219] In some embodiments, based on knowledge of the elemental composition of the polymer and filler, the mixing ratio can be calculated to achieve a desired C:N ratio of the biodegradable composition; and / or the concentrations of the various elements so desired and mentioned herein in the biodegradable composition.

[0220] Fillers will generally be provided in sufficient concentrations to achieve the desired C:N ratio of the biodegradable composition; and / or the concentration of the various elements so desired and mentioned herein in the polymer. Therefore, the concentration of fillers should not be considered restrictive. It may be convenient to provide the concentration of fillers as a percentage (% w / w) of the total biodegradable composition on a weight-to-weight basis. In some embodiments, fillers may be present up to 90% w / w, such as up to 80% w / w, such as up to 70% w / w, such as up to 60% w / w, such as up to 50% w / w, such as up to 40% w / w, such as up to 30% w / w, such as up to 25% w / w, such as up to 20% w / w, such as up to 15% w / w, such as up to 10% w / w, such as up to 5% w / w. In some embodiments, the filler is present in a concentration of at least 0.01% w / w, such as at least 0.1% w / w, such as at least 1% w / w, such as at least 2% w / w, such as at least 3% w / w, such as at least 4% w / w, such as at least 5% w / w, such as at least 6% w / w, such as at least 7% w / w, such as at least 8% w / w, such as at least 9% w / w, such as at least 10% w / w. In some embodiments, the filler is present in a concentration of about 10% w / w, such as a concentration of 10% w / w.

[0221] The particle size of filler should not be considered as limiting, although usually filler will have an average particle size of 1nm to 5mm. In some embodiments, the average particle size that filler has will be 100nm to 1mm. Typically, the maximum particle size that filler has will be 10nm to 5mm. In some embodiments, the maximum particle size that filler has will be 100nm to 1mm, such as 1μm to 500μm. In some embodiments, the maximum particle size of filler will be about 500μm, such as 500μm. In some cases, the filler source will have a desired particle size, although post-processing will be required in some cases. Technicians will easily understand the technology of producing particulate matter with a desired particle size, and include particle size reduction technology such as grinding / milling (and optionally sieving) and particle size enlargement technology such as wet and dry granulation (and optionally sieving).

[0222] In some embodiments, fillers (such as blood and bone) can be graded by sieving with a sieve of a desired size, such as a sieve that sieves out particles larger than 1 mm, such as larger than 850 μm, such as an 850 μm sieve, so that finer particles can be used in the biodegradable compositions of the present invention. In some embodiments, the sieve can have even smaller holes. It has been found that for some biodegradable compositions, finer filler particles, such as 1 μm to 500 μm, are more suitable for molding techniques, such as injection molding.

[0223] The biodegradable composition of the present invention can be formed using a wide range of techniques, including 3D printing. In this molding mode, the biodegradable composition can be passed through a nozzle having, for example, a 0.75 mm or smaller aperture. It should be understood that the filler particle size should generally be (substantially) smaller than the aperture size of the nozzle. For example, a filler size of about 250 microns can be used to reduce or eliminate the possibility of (one or more) filler particles clogging the nozzle.

[0224] In some cases, the filler source will undergo other post-processing steps, such as being subjected to: temperature regulation (such as exposure to a temperature above ambient temperature for a period of time, such as to reduce moisture content); pressure regulation (such as extrusion); and / or chemical modification (such as digestion, such as to facilitate faster decomposition).

[0225] In a preferred embodiment, the biodegradable composition comprising a polymer and a filler comprises a mixture of PBS, PLA and a filler. In such an embodiment, the components PBS, PLA and filler may be present in the following proportions:

[0226] a ratio of about 40:50:10 to about 50:40:10, such as 40:50:10 to 50:40:10, such as about 45:45:10, such as 45:45:10; or

[0227] a ratio of about 65:25:10 to 55:35:10, such as 65:25:10 to 55:35:10, such as about 60:30:10, such as 60:30:10; or

[0228] a ratio of about 65:30:5 to about 60:35:5, such as 65:30:5 to 60:35:5, such as about 62.5:32.5:5, such as 62.5:32.5:5; or

[0229] a ratio of about 60:25:15 to about 55:30:15, such as 60:25:15 to 55:30:15, such as about 57.5:27.5:15, such as 57.5:27.5:15; or

[0230] A ratio of about 57.5:22.5:20 to about 52.5:27.5:20, such as 57.5:22.5:20 to 52.5:27.5:20, such as about 55:25:20, such as 55:25:20.

[0231] A ratio of PBS:PLA:filler of about 60:30:10 (such as 60:30:10) is particularly preferred. That is, similar (or identical) ratios of the following polymer compositions are also preferred: PBAT / PLA; PHBV / PLA; and PCL / PLA.

[0232] As used herein, the term "about" in relation to a specific value (or multiple values) generally refers to a range of numerical values, such as plus or minus 15% of the specific value (or each of the multiple values), such as plus or minus 10% of the specific value (or each of the multiple values), such as plus or minus 5% of the specific value (or each of the multiple values), such as plus or minus 3% of the specific value (or each of the multiple values), such as plus or minus 2% of the specific value (or each of the multiple values), such as plus or minus 1% of the specific value (or each of the multiple values). For example, the expression "about 60:30:10" may refer to a range of (54 to 66):(27 to 33):(9 to 11), where "about" indicates a range of values, such as plus or minus 10%.

[0233] In some embodiments, the term "about" in connection with a particular value (or values) refers to a numerical range corresponding to those values ​​rounded to the specified number of significant figures - for example, the expression "about 60:30:10" can refer to the range of (59.50 to 60.49):(29.50 to 30.49):(9.50 to 10.49).

[0234] As described above, the biodegradable compositions of the present invention can be used in a variety of products. Techniques that can be used to blend fillers and polymers and shape them into desired products include additive manufacturing, extrusion, thermoforming, injection molding, rotational molding, injection blow molding, vacuum casting, vacuum forming and / or compression molding.

[0235] For example, the biodegradable composition of the present invention can be extruded into a desired product, such as a container defining a cavity. Alternatively, an additive layered manufacturing process can also be used to build the shape of a product such as a container defining a cavity. It is also contemplated that a molding process, such as sacrificial molding or an injection molding process or thermoforming can be used.

[0236] In some embodiments, a twin-screw extruder is used to process the biodegradable composition by extrusion to reduce production costs through process simplification and to minimize degradation of physical properties after the addition of fillers. The biodegradable composition can be prepared using standard extrusion equipment - Labtech 26mm scientific twin-screw, co-rotating extruder LTE26-40.

[0237] The mixture of polymer and filler can be extruded into sheet using a co-rotating extruder (LTE26-40, 40 L / D ratio) provided with a slot die and a LabTech roll calender. An exemplary die pressure is 25 to 35 bar. The sheet formed in this manner is collected into a roll from the extruder and then stored before thermoforming.

[0238] A 3D printed mold of the desired product shape (such as a plant tray) can be prepared for the thermoforming step. Sheets (such as extruded sheets) can be thermoformed using standard vacuum forming equipment such as the Steele FS44. In order for the vacuum to penetrate the mold, a series of vent holes (such as drilled holes) can be included in the mold. The sheet can first be heated until soft and then placed on the mold to form the product (such as a plant tray).

[0239] The present invention also provides a method for selecting a filler to prepare a biodegradable composition comprising a polymer, the method comprising the steps of:

[0240] i) selecting a polymer;

[0241] ii) determining the C:N ratio of the polymer;

[0242] iii) Selecting a filler of known C:N ratio such that when combined with the polymer, the C:N ratio of the combined filler and polymer is from 30 to 200.

[0243] For example, if the selected polymer contains carbon but no nitrogen (100:0 C:N), and the selected filler contains 95:5 C:N, then mixing the two in equal amounts will produce a mixture with a C:N ratio of 195:5, which is equivalent to 39, which falls within the range of 30 to 200.

[0244] Using this approach, customized fillers can be created, including through the combination of two or more conventional fillers, such as those indicated above.

[0245] It should be understood that similar methods can be used to select fillers to prepare biodegradable compositions having concentrations of the various elements so desired and mentioned herein (such as phosphorus, potassium, etc.) in the biodegradable composition.

[0246] Furthermore, the inventors have found that the addition of fillers also provides improved manufacturability, i.e. during the extrusion / thermoforming process. It has been found that the addition of fillers increases the Young's modulus of the composition to a preferred level (about 1.298 GPa) to allow improved processing. Initial tests have shown that a ratio of 60:30:10 (PBS:PLA:filler) provides mechanical strength similar to that of HIPS (high impact polystyrene) and can therefore be used as a suitable biodegradable composition for replacing HIPS in products made from this polymer.

[0247] By way of non-limiting example only, aspects of the present invention will be described with reference to plant containers / trays formed from a biodegradable composition.

[0248] Containers suitable for biodegradation when buried in soil under non-industrial composting conditions

[0249] The biodegradable composition may be formed into a plant container. Those skilled in the art will appreciate that the shape and / or configuration of the plant container may be adapted to promote plant growth and / or enhance degradation of the container after planting in soil. Figure 1-4 A plant container (100) is depicted that includes a drainage hole (20) on the base of the container to allow excess water to drain. The drainage holes are generally circular in nature; however, it should be understood that these holes should not be limited to such, and holes of any shape may be used with the container of the present invention.

[0250] The container (100) may include a series of elongated slits (10) around the periphery of the container. The slits generally extend vertically from the bottom of the container and may vary in size in terms of length and width of the slits. The slits (10) are configured so that once the container is planted in the ground, the roots of the plant can penetrate the wall of the container. In addition, the slits provide sections in which the container can decompose once planted, thereby further accelerating degradation.

[0251] It should be understood that the number, size and position of the slits may vary depending on the size of the container. However, it should be noted that the container will be configured to retain soil and plants within the container.

[0252] Alternative plant containers / trays are also shown in Figure 5-6 Aspects of the container are similar to those of the plant container described above and similar reference numerals refer to similar parts.

[0253] Example

[0254] The invention will now be described with reference to the following compositions prepared for use in plant containers. However, such examples should not be viewed as limiting the scope of the invention.

[0255] Biodegradation Study 1

[0256] Example 1

[0257]

[0258] Example 2

[0259] Amount (w / w%) Notes PBS 60 PLA 30 filler 10 In this example, commercial "blood and bone" fertilizer was used.

[0260] Example 3

[0261] Amount (w / w%) Notes PBS 60 PLA 30 filler 10 Commercial grade sheep dung balls (ground)

[0262] Example 4

[0263] Amount (w / w%) Notes PBS 60 PLA 30 filler 10 starch

[0264] Example 5

[0265] Amount (w / w%) Notes PBS 60 PLA 30 filler 10 Kiwi "hair" - cyclone dust

[0266] Example 6

[0267]

[0268] Example 7A

[0269]

[0270] Example 7B

[0271]

[0272] Example 8A

[0273]

[0274]

[0275] Example 8B

[0276]

[0277] Example 8C

[0278]

[0279] Example 8D

[0280]

[0281] Example 9A

[0282]

[0283]

[0284] Example 9B

[0285]

[0286] Manufacturing method

[0287] Thermoforming

[0288] Initial testing indicated that Examples 1 and 2 possessed the necessary properties to enable them to be thermoformed and become "Tube A" and "Tube B" referred to below in the indoor degradation testing.

[0289] Injection Molding

[0290] Additional compositions (Examples 7B, 8B-8D and 9B above) with injection molding grade materials were also manufactured into individual pots by injection molding. This was successful and two individual pots were produced and are considered suitable for large scale production.

[0291] The testing involved developing five injection molding compositions (Examples 7B, 8B-8D, and 9B) using specific injection molding grades with varying percentages of PBS and PLA, and incorporating two different fillers in the process, one containing "fish meal" and one containing "blood and bone."

[0292] Of the five compositions prepared above, Examples 7B and 8D are considered commercially feasible to produce by injection molding.

[0293] It will be appreciated by those skilled in the art that different grades of starting materials may be used depending on the manufacturing method. For example, the grade of PLA, PBS or filler may vary depending on the manufacturing method used.

[0294] Degradation test

[0295] Plant containers prepared according to the invention were produced and tested in this experiment. The compositions disclosed in Examples 1 and 2 were used to prepare the plant containers.

[0296] The purpose of the trial was to investigate the rate and type of decomposition of the plant containers of the invention under "normal" use conditions. Both above-ground and below-ground trials were conducted. The trials were conducted under New Zealand spring time conditions (September to November).

[0297] It will be appreciated that commercial plant nurseries are often very humid environments. It is believed that this additional moisture may have contributed to faster degradation of the containers in this experiment.

[0298] Trial 1 - Commercial Nursery

[0299] Two different compositions were tested in an above ground commercial nursery setting. Figure 7-9 Degradation of the container after approximately 60 days of use is shown.

[0300] like Figure 7-8 As shown, in the test, containers made from composition Example 1 showed visual signs of degradation after 60 days. This suggests that the composition may be useful for plants that grow for a shorter period of time above ground.

[0301] refer to Fig. 9 , the container made from Composition Example 2 showed minimal visual biodegradation after 60 days. This suggests that the composition may be suitable for plants growing for a long time in the ground.

[0302] Around the same time, another sample was sent to a testing facility for additional detailed testing of biodegradation. It was noted at that time that there were no visible signs of degradation after 60 days, possibly because the conditions in the testing facility were more controlled than those in commercial nurseries, which may have higher humidity levels.

[0303] Test 2 - Home / Underground Test

[0304] A home, in-ground trial was conducted. Tomato seedlings were planted in two containers prepared from composition examples 1 and 2, and two containers were subsequently planted.

[0305] Figure 10-11 The degradation of a container made from Composition Example 1 after approximately 7 weeks in-ground is shown.

[0306] Figure 12-13 The degradation of a container made from Composition Example 2 after approximately 7 weeks in-ground is shown.

[0307] In the underground trials, both containers showed good degradation by visual inspection after only 42 days of planting in the ground.

[0308] From initial observations of the plants, it was observed that plant growth was active and the plant matter appeared generally healthy. It was observed that there was an overall improvement in the growth characteristics of the plants grown in the ground using the containers of the present invention compared to previous plants.

[0309] Test 3 - Biodegradation Test

[0310] The samples were sent to a laboratory testing facility (Scion, Titokorangi Drive, Rotorua 3046, New Zealand) for detailed testing to determine the biodegradation of the samples as described in Trial 1. Three samples were tested in accordance with AS 5810 at 25°C (which is the standard for testing under home composting conditions).

[0311] The test facility tested the aerobic biodegradation of sample materials in activated vermiculite according to ISO standard 14855-1 (2012) at home composting conditions at 25°C.

[0312] Two different compositions with different fillers are tested in combination with control samples. These two compositions include PBS and PLA and the polymer blend of different fillers, and this filler includes starch (sample 1) and blood and bone (sample 2) respectively. The control sample is made up of the mixture of PBS and PLA. Each sample is tested in triplicate, and the mean value of each sample is calculated, and the result is shown in Table A and Table B below.

[0313] The biodegradable compositions of the present invention (Examples 2 and 4) passed the 10-day and 45-day validation requirements specified in ISO 14855-1 (2012), indicating satisfactory microbial activity of the compost inoculant.

[0314] Table A. Medium term biodegradation percentage after 58 days at 25°C (average of three replicates).

[0315]

[0316] Table B. Medium term biodegradation percentage after 112 days at 25°C (average of three replicates).

[0317]

[0318]

[0319] According to AS5810 (2010), a test material can be considered biodegradable when 90% has been biodegraded within 365 days or when the biodegradation has reached 90% of the maximum biodegradation of cellulose (positive control). The maximum biodegradation percentage of the positive control can only be obtained after the biodegradation rate reaches a plateau.

[0320] As shown in Table C, the PBS / PLA composite and the PBS / PLA / starch composite biodegraded very little during the 190-day test period. The PBS / PLA / blood and bone composite did biodegrade more effectively than the PBS / PLA or PBS / PLA / starch composites. After 190 days, the test material had reached 97.5% of the biodegradability achieved by cellulose. However, please note that the positive control cellulose and the PBS / PLA / blood and bone composite had not yet reached the plateau value, so further degradation is expected to occur after 190 days.

[0321] Table C. Medium term biodegradation percentage after 190 days at 25°C (average of three replicates - treatments were tested in triplicate, but one replicate of the PBS / PLA composite broke down at day 113).

[0322]

[0323] As can be seen, the biodegradable compositions of the present invention (Examples 2 and 4) show a dramatic improvement in biodegradation compared to the control, in particular the results show that the levels of biodegradation of the biodegradable compositions of the present invention (Examples 2 and 4) are at least twice that of the control samples (after 58 and 112 days), while the preferred biodegradable compositions of the present invention comprising blood and bone fillers degrade 38 times faster than the control samples (after 112 days), and significantly faster than the compositions comprising starch. From the results shown after 112 and 190 days, the levels of biodegradation of the preferred biodegradable compositions of the present invention comprising blood and bone fillers are substantially the same as the positive control (cellulose), which is surprising considering the inclusion of PLA, which is not expected to be significantly biodegraded even when co-formulated with PBS, as shown in the negative control.

[0324] Biodegradation Study 2

[0325] An additional series of 29 compositions were prepared and tested, some of which were exposed to soil for periods of 0, 2, 4 or 6 months to evaluate biodegradation under non-industrial composting conditions.

[0326] In general, the samples tested had the following variable parameters:

[0327] Type of polymer grade: Thermoforming (TF) or Injection Molding (IM)

[0328] PBS / PLA / filler ratio: 65:35:0 (no filler), 60:30:10 or 45:45:10

[0329] Types of filler materials (all 10% w / w): starch, blood & bone, fish meal, canola, soybean meal and feather meal

[0330] Buried in soil for 0, 2, 4 or 6 months.

[0331] For different production processes, different grades of PBS and PLA are used. For thermoforming applications, the PBS grade is FD92 and the PLA grade is 2003D, while for injection molding applications, the PBS grade used is FZ71 and the PLA grade is 3052D.

[0332] Not every combination of the above treatments was investigated in this study. Due to the number of samples available for soil treatments, some replicates were combined for tests that required a large number of test samples. Table 1 shows the samples analyzed and the specific analyses performed. Tests were run in triplicate where sample quantity permitted.

[0333] The following selected tests were performed on the samples:

[0334] Microscopic analysis,

[0335] Fourier transform infrared spectroscopy (FTIR),

[0336] Gel Permeation Chromatography (GPC),

[0337] Carbon (C), nitrogen (N) and C:N ratio,

[0338] Total and extractable N, P, and K were analyzed by: Total Kjehldahl Nitrogen (TKN), Total P, Total K, 2M KCl extractable NH4, and Mehlich 3 (P, K, Ca, Mg, Na, Al, Fe, B, Cu, Mn, and Zn) analysis.

[0339] Table 1: Description of the test specimens and the analyses performed on them. TF = Thermoforming grade, IM - Injection molding grade.

[0340]

[0341] Microscopy

[0342] A number of samples were subjected to microscopic (SEM) analysis and the results are summarized in Table 2 and shown in Figures 14 to 22 middle.

[0343] Table 2: Samples examined by SEM imaging

[0344]

[0345]

[0346] Composites containing starch granules, blood & bone, and fish meal were clearly distinguishable from composites without fillers. Starch granules could be easily seen both inside and on the surface of the composite pellets. Also, the composite pellets containing blood & bone or fish meal contained larger particles of various sizes compared to the uniform starch granules.

[0347] After 4 to 6 months of soil exposure, the samples showed signs of degradation in the form of cracks or small holes. The fillers at the surface may degrade or affect the degradation of the polymer. The fillers at the composite surface appear to be covered by the polymer, so the amount directly exposed to the soil may have been minimal. All three fillers (blood & bone, fish meal and starch) showed poor contact with the polymer, with void spaces around the fillers in the matrix.

[0348] Fourier Transform Infrared Spectroscopy (FTIR)

[0349] FTIR spectroscopy provides a signature of the key chemical composition of the test composition, and therefore, the signature will only change significantly if the molecular composition changes significantly.

[0350] The samples were analyzed by Fourier transform infrared spectroscopy in attenuated total reflectance mode (FTIR-ATR) using 64 samples and the wavelength range was from 4000 to 400 cm -1 At 4cm -1 Background scan at resolution.

[0351] Most of the FTIR peaks are very similar between all measured spectra. This indicates that there are no major changes in the key chemical composition within the molecules of the tested materials. However, minor differences were observed. Ester bonds are present in both PBS and PLA, but they are located at different wavelengths. 1755cm -1 The peak represents the carbonyl stretching of PLA ester, while 1711 cm -1 The peak represents the carbonyl stretching of the PBS ester.

[0352] Qualitative observation of these peak positions showed that in the thermoforming grade formulation 60:30 PBS / PLA with blood & bone filler, not only the 1755 cm -1 The peak after soil exposure (sample ID#11, #12, and #13) is lower than that before soil exposure (sample ID#3), and the peak at 1711 cm -1 The peak after soil exposure is also lower than that before soil exposure. -1 peak (PLA ester) and 1711cm -1 The ratios of the peaks (PBS esters) were used for interpretation (Table 3).

[0353] The data in Table 3 are derived from FTIR spectra obtained from the samples analyzed.

[0354] For the thermoforming grade formulation 60:30 PBS / PLA with blood & bone filler, the PLA / PBS peak ratio increased in the first 4 months. A possible explanation for this is that PBS degrades faster than PLA, increasing the peak ratio. After 6 months, the peak ratio decreased, possibly indicating that PLA also began to degrade.

[0355] For the other composites, FTIR peak ratios were measured only at 0 and 6 months. The thermoformed 45:45 PBS / PLA with Blood & Bone filler (Sample ID #20) did not increase the peak ratio compared to the thermoformed composite without filler and the composite of 60:30:10 PBS / PLA with Blood & Bone filler (Sample ID #3). The injection molded formulations 45:45 PBS / PLA with Blood & Bone (Sample ID #8 and #21), starch (Sample ID #9 and #22), and fish meal (Sample ID #10 and #23) as fillers all increased their peak ratios over time, thus potentially indicating degradation of the composites, but there was insufficient data to determine if it was the PBS that degraded or the PLA that also degraded.

[0356] Including 1711cm -1 Peak and 1755cm -1 Quantitative analysis by peak picking of the peaks and additional FTIR analysis of the composites exposed for 2 and 4 months can give more detailed information on the degradability of these composites.

[0357]

[0358]

[0359] Gel Permeation Chromatography (GPC)

[0360] Gel Permeation Chromatography (GPC) is a type of size exclusion chromatography and provides molecular weight data for polymers by separating analytes according to size.

[0361] All samples described in Table 1 were analyzed for their respective molecular weight distributions after dissolving known masses of the samples in chloroform. The fillers were generally insoluble in chloroform, as evident from the precipitate remaining after the dissolution process.

[0362] The parameters measured using GPC analysis that are of most value for this study are the mass-weighted molecular weight (Mw) and the dispersity index. Mw does not directly average the mass of the individual polymers like the number average molecular weight (Mn), but rather takes into account the overall molecular weight of all polymers in the sample. It is based on the fact that larger sized molecules contain more mass than smaller molecules and therefore contribute too much to the molecular weight average. Unlike the Mn average, the Mw average takes into account the molecular size of the polymers, not just the number of polymers in the sample, and therefore provides a more informative representation of the molecular weight of the sample.

[0363] The dispersity index is the ratio between Mw / Mn and for a completely homogeneous sample its value is 1. The larger the dispersity index, the greater the size range of the polymers in the sample.

[0364] The melt mass flow rate (MFR), also known as melt index, describes the flow characteristics of a plastic at a specified temperature. The melt flow rate is a measure of how easily a molten plastic flows. The MFR is related to the relative molecular weight of the polymer. The theoretical MFR of the biopolymers used in this study is shown in Table 4. In theory, if the MFR of a given polymer is higher, the molecular weight (Mw) is lower and vice versa. Therefore, based on the MFR index in Table 4 and actual measurements, the thermoforming grades show higher Mw than the injection molding grades for the corresponding polymers.

[0365] Table 4: Theoretical melt flow index (MFR), mass weighted molecular weight (Mw) and dispersity index of the base polymers used in the composites in this study.

[0366]

[0367] Effect of polymer grade on molecular weight of composites

[0368] To obtain an indication of the effect of polymer grade on the molecular weight of the composites, the blending ratios of the composites were used to calculate theoretical Mw masses. These calculations were based on the assumption that no filler material would dissolve in chloroform. The Mw measured on the composites after processing but before soil incubation were averaged by polymer grade to compare them with the theoretical Mw before compounding (Table 4).

[0369] This shows that the compounding step did not affect the Mw of the injection molding grade composites, while for the thermoforming type materials, the compounding process reduced the Mw of the composites by 27% to 37% (Table 5).

[0370] However, since the Mw of the thermoformed plastics before compounding was higher than that of the injection molded plastics, the average Mw of all fillers for each processing type after compounding was comparable (Table 5).

[0371] Table 5: Theoretical mass weighted molecular weight (Mw) and GPC measured Mw averaged over all fillers for various processing types and blend ratios in this study, and the percentage reduction due to processing, NA = not measured.

[0372]

[0373]

[0374] Effect of filler type, blending ratio and soil incubation period

[0375] The Mw by processing type grade, blending ratio and filler type showed that the composites with various fillers ranged between 101,115 g / mol (fish meal) and 129,050 g / mol (blood & bone) before soil incubation (Table 6).

[0376] After 6 months of soil exposure, the Mw of the injection molded type (45:45 blend ratio) starch composite decreased by 18%, the blood & bone composite decreased by 21%, and the fish meal composite decreased by 37%. During the same soil exposure period, the Mw of the thermoformed type (60:30 blend ratio) blood & bone composite decreased by 55%.

[0377] For both injection molded and thermoformed blood & bone composites, there was no significant decrease in Mw as soil exposure time increased from 2 to 6 months, while only a small decrease was observed for injection molded fish meal and starch composites. This may indicate that microbial activity and most of the degradation of polymer chains occurred within the first few months.

[0378] After 6 months of soil exposure, the thermoformed blood & bone type composites with a blend ratio of 60:30:10 showed an Mw value of about half that of the Mw value of the similar composites with a blend ratio of 45:45:10. A possible explanation for the higher Mw of the 45:45:10 blend is the larger amount of PLA present in the composite. PLA polymers are known to biodegrade more slowly than PBS polymers. Therefore, a larger proportion of PLA in the composite may slow down the biodegradation process.

[0379] Table 6: Mass weighted molecular weight (Mw) and (standard deviation) for different processing types, blending ratios, filler types and soil incubation periods measured in this study, where "(-)" means "not measured". All samples except the thermoformed 60:30 blood & bone composites incubated in soil had a sample size of 2. Their sample size was 6.

[0380]

[0381]

[0382] The lower dispersibility index shows a more uniform sample than when the dispersibility index value is higher. Before soil exposure, the dispersibility index of injection type composite materials is higher than those composite materials intended for thermoforming applications. However, thermoforming type starch composite materials approach the dispersibility value of suitable composite materials for injection molding. Thermoforming type composite materials with other fillers all show lower dispersibility indexes, ranging from 8.9 (blood & bone) to 10.0 (fish meal) (Table 7).

[0383] After 6 months of soil exposure, the thermoformed blood & bone composite with a blend ratio of 60:30:10 achieved the lowest dispersibility index. All 45:45:10 blend ratios showed larger dispersibility indices, ranked from low to high as follows: injection molded fish meal composite < injection molded blood & bone composite < injection molded starch < thermoformed blood and bone (Table 7).

[0384] Table 7: Average dispersibility index and (standard deviation) for different processing types, blending ratios, filler types and soil incubation periods measured in this study, where "(-)" means "not measured". All sample sizes were 2 except for the thermoformed 60:30 blood & bone composites incubated in soil. Their sample size was 6.

[0385]

[0386] Carbon to Nitrogen Ratio

[0387] The carbon content of the composites with various filler types ranged from 52.3% to 57.6% (Table 8), indicating that filler type had only a small effect on the carbon content of the composites prior to soil incubation. The range of nitrogen content varied more significantly than the carbon content. N content ranged from almost nothing (0.05%) for fillers known to not contain any nitrogen to 1.53% N for feather meal (Table 9).

[0388] After soil exposure, both carbon and nitrogen contents decreased. However, for the injection molded and thermoformed compositions including blood & bone fillers, the carbon content was stable with increasing soil exposure time, while nitrogen continued to decrease with soil exposure time. This is also reflected in the increasing C to N ratio of the blood & bone composites over time. This result may indicate that the nitrogen provided (in this case by blood and bone) is accessible to the microbial community and has been metabolized to some extent by those microbial communities.

[0389] Table 8: Carbon content for different processing types, blending ratios, filler types and soil incubation periods measured in this study, where "(-)" means "not measured". The standard deviations of the thermoformed 60:30 blood & bone composites in soil incubations analyzed in triplicate are given.

[0390]

[0391] Table 8: Carbon content for different processing types, blending ratios, filler types and soil incubation periods measured in this study, where "(-)" means "not measured". The standard deviations of the thermoformed 60:30 blood & bone composites in soil incubations analyzed in triplicate are given.

[0392]

[0393]

[0394] Table 10: Carbon and nitrogen ratios for different processing types, blending ratios, filler types and soil incubation periods measured in this study, where "(-)" indicates "not measured". The standard deviations of the thermoformed 60:30 blood & bone composites in soil incubations analyzed in triplicate are given.

[0395]

[0396] Total and extractable nitrogen, phosphorus and potassium concentrations

[0397] Total P and K are analyzed by a digestion method that allows the entire sample to be dissolved prior to quantifying those nutrients (Table 11). Total N can be determined using a very high temperature furnace. These results are reported in the previous section (Table 9), but analysis using the total Kjehldahl nitrogen (TKN) digestion is more accurate. Extractable nitrogen will be measured as extractable ammonium.

[0398] In addition, extractable nutrients were analyzed (Table 12) because they show the availability of those nutrients once the composites are exposed to the soil. Mehlich 3 was selected as the extraction method. This method uses the acids acetic acid and nitric acid. The Mehlich 3 extraction process is most commonly used to determine the availability of soil macronutrients (phosphorus, calcium, magnesium, and potassium) and soil micronutrients (copper, zinc, manganese, and iron).

[0399] Before soil exposure, the blood & bone and fish meal composites processed by thermoforming and injection molding end-use applications contained significantly more phosphorus than the other fillers (Table 11), while the feather meal of the thermoforming type contained the most nitrogen (Table 9). The most total and extractable K and B were present in soybean meal, while blood & bone contained significantly more Ca and Fe than the composites with the other fillers. The composites with rapeseed contained the most extractable Mg, Mn, Zn, and Cu.

[0400] For the composites with fish meal filler and blood & bone filler, the extractable P% and extractable K% increased after soil exposure compared to the composites before soil exposure. Thermoforming grade blood & bone filler increased more in extractable P and K percentage than injection molding grade blood & bone filler. This indicates that more P and K became available with increasing soil exposure (Table 11). In addition, except for extractable sodium of thermoforming blood & bone, all other extractable nutrients also increased after soil exposure (Table 12). This provides evidence that the composites decompose in the soil environment.

[0401] Table 11: Total phosphorus (TP), extractable phosphorus (Extr. P), total potassium (TK) and extractable potassium (Extr. K) for different processing types, blending ratios, filler types and soil incubation periods measured in this study. The standard deviations of the thermoformed grade 60:30 blood & bone composites analyzed for TP and TK in triplicate are given.

[0402]

[0403]

[0404] Table 12: Extractable calcium (Ca), magnesium (Mg), sodium (Na), manganese (Mn), iron (Fe), aluminum (Al), zinc (Zn), copper (Cu), and boron (B) for different processing types, blending ratios, filler types, and soil incubation periods measured in this study. The sample size for all samples was 1.

[0405]

[0406]

[0407] Summarize

[0408] Chemical, spectroscopic and image analysis were performed on 10 different polybutylene succinate (PBS) / poly(lactic acid) (PLA) composites containing biomaterial fillers, made from thermoforming or injection molding grade polymers using the following PBS / PLA / filler ratios: 65:35:0 (no filler), 60:30:10 or 45:45:10. Filler materials were: starch, blood & bone, fish meal, rapeseed, soybean meal and feather meal

[0409] Small strips of selected treatments (Starch, Blood & Bone, and Fish Meal composites) were also buried in peat soil for 2, 4, or 6 months. After the soil exposure period, samples were taken from the soil and submitted to Scion for analysis. A total of 29 PBS / PLA composites were analyzed. All strips were produced by injection molding, even for the thermoforming formulations. This was to obtain similar and homogenous samples for testing.

[0410] Microscopy showed that the fillers (blood & bone, fish meal and starch) showed poor contact with the polymer, with voids around the fillers in the matrix. This may have aided the degradation process. After 4-6 months of soil exposure, the composites showed signs of degradation in the form of cracks or small holes.

[0411] Fourier transform infrared spectroscopy (FTIR) showed that all composites had similar chemical fingerprints, which was expected since they were all composed primarily of PBS and PLA. However, minor differences were observed. -1 The peak represents the carbonyl stretching of PLA ester, while 1711 cm -1 The peak represents the carbonyl stretching of the PBS ester.

[0412] Qualitative observation of the peak positions showed that in the thermoforming grade formulation 60:30 PBS / PLA with blood & bone filler, 1755 cm -1 Peak and 1711cm -1 The peaks after soil exposure were lower than those before soil exposure. -1 peak (PLA ester) and 1711cm -1 The ratio of peaks (PBS esters) showed an increase in the PLA / PBS peak ratio in the first 4 months, followed by a decrease after 6 months. This may indicate that PBS degraded faster in the beginning, while PLA began to degrade in the last few months. However, more time series of measurements of composites exposed to soil need to be analyzed before conclusions about PLA degradation can be firmly established.

[0413] Gel permeation chromatography (GPC) analysis showed that polymer grade had an effect on molecular weight. The results showed that the compounding step did not affect the weighted molecular weight (Mw) of the injection molding compound formulations, but it reduced the Mw of the thermoforming compound by 27% to 37%. However, since the Mw of the thermoforming plastic was higher than that of the injection molding plastic before compounding, the average Mw of all fillers for each processing type after processing was comparable.

[0414] After 6 months of soil exposure, the Mw of the injection molded (45:45 blend ratio) starch composite decreased by 18%, the blood & bone composite decreased by 21%, and the fish meal composite decreased by 37%. During the same soil exposure period, the Mw of the thermoformed (60:30 blend ratio) blood & bone composite decreased by 55%. The lower drop in Mw for the 45:45:10 blend may be due to the larger amount of PLA in the composite rather than the preparation method. PLA is known to biodegrade more slowly than PBS under environmentally relevant conditions. Therefore, a larger proportion of PLA in the composite may slow the biodegradation process. Increasing the soil exposure from 2 months to 6 months did not show a clear trend in molecular weight loss.

[0415] Filler type had a large effect on the nitrogen concentration of the composites, but only a small effect on the carbon concentration. The feather meal composites contained the highest concentration of nitrogen. The fish meal composites contained the second highest concentration of nitrogen. Blood & bone and fish meal composites produced with both thermoforming and injection molding grades contained significantly more phosphorus than the composites with the other fillers.

[0416] After initial soil exposure, the carbon and nitrogen contents of the composites both decreased. However, for both injection molded and thermoformed blood & bone fillers, the carbon content was stable with increasing soil exposure time, while nitrogen continued to decrease with soil exposure time. This is also reflected in the increasing C to N ratio of the blood & bone composites over time. This result may indicate that the nitrogen provided by blood and bone is accessible to microbial communities and has been metabolized to some extent by those microbial communities.

[0417] Most of the extractable nutrients increased after soil exposure, indicating that more nutrients became available, signaling that the composites decomposed in the soil environment. Composites with fish meal filler and blood & bone filler increased the percentage of extractable P and extractable K, while the starch composite did not.

[0418] Thermoformed composites (60:30 blend ratio) with blood & bone filler showed greater increases in extractable P and K percentages than the injection molded (45:45 blend ratio) blood & bone filler composites. This indicates that the thermoformed (60:30 blend ratio) blood & bone filler composites are further degraded compared to the injection molded (45:45 blend ratio) blood & bone filler composites.

[0419] Impact and Conclusion

[0420] Overall, this study showed the degradation of the composites after soil exposure, especially for the composites containing blood & bone and fish meal. Feather meal composites were not tested for soil exposure in this study but may have good degradation potential because they contain the highest nitrogen content of all filler types. Finally, the 60:30 blend ratio degraded further compared to the 45:45 blend ratio, possibly due to the higher content of PBS, which is more degradable than PLA.

[0421] Biodegradation Study 3

[0422] A series of compositions were prepared and tested, some of which were exposed to soil for periods of 0, 2, 4 or 6 months to evaluate biodegradation under non-industrial (home) composting conditions.

[0423] Figures 23 to 36 The sample shown is a sample inserted into the soil on June 25, 2021. The number sequence on the samples reflects when the samples were recovered from the soil, with the smallest number being at 2 months, the middle number at 4 months, and the largest number at 6 months, with three samples for each month.

[0424] Table D: The table below shows the average weather conditions by month and cumulatively.

[0425]

[0426] Biodegradable composition A- Fig.23

[0427]

[0428] Biodegradable composition B- Fig.24

[0429]

[0430] Biodegradable composition C- Fig.25

[0431]

[0432] Biodegradable composition D- Fig.26

[0433]

[0434]

[0435] Biodegradable composition E- Fig. 27

[0436]

[0437] Biodegradable composition C- Fig.28

[0438]

[0439]

[0440] Biodegradable composition D- Fig.29

[0441]

[0442] Composition D1- Fig.30

[0443]

[0444] Biodegradable composition D2- Fig.31

[0445]

[0446] Biodegradable composition E- Fig.32

[0447]

[0448] PBS-only Fig.33

[0449]

[0450] PBS 60% PLA-40%- Fig.34

[0451]

[0452] 6 Months of Samples of All Eight Formulas - Fig.35

[0453] 6 Month Results for Other Formulas - Fig.36

[0454] Biodegradation studies 4

[0455] In the current study, we examined the following materials:

[0456] Composites made from combinations of PLA with different fillers (added at 10 wt.%). The fillers were blood and bone, fish meal, feather meal, rapeseed meal. A control of 100% PLA was also used (turning point 2);

[0457] Composites made of PBS / PLA / blood and bone (60 / 30 / 10 wt.%);

[0458] Composites using other plastics including polybutylene terephthalate adipate (PBAT), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), and polycaprolactone (PCL): PBAT / PLA / blood and bone, PHBV / PLA / blood and bone, PCL / PLA / blood and bone, PBS / PLA / feather meal (60 / 30 / 10 wt.%) (turning point 3);

[0459] • Blends of PBS / PLA / blood and bone with different blood and bone ratios: (62.5 / 32.5 / 5 wt. %), (57.5 / 27.5 / 15 wt. %), (55 / 25 / 20 wt. %) (QT 10336).

[0460] The above formulations were extruded using injection molding grade PLA polymer Luminy 1130 and injection molding grade PBS polymer BioPBS FZ71.

[0461] Methods and experimental design

[0462] A total of 13 different formulations were tested (see table below). These formulations were then exposed to soil for: 0, 3, 4 or 6 months; or 0, 3 and 6 months; or 0, 2, 4 and 6 months to determine whether some fillers or different combinations of composite types might promote the degradation process under ambient conditions.

[0463] The following selected tests were performed on the samples:

[0464] Visual and microscopic analysis,

[0465] Fourier transform infrared spectroscopy (FTIR) at 0 and 6 months,

[0466] Gel Permeation Chromatography (GPC),

[0467] Mass, carbon (C), nitrogen (N) and C:N ratio,

[0468] Total P, total K, extractable NH4 (extraction with 2M KCl) and extractable P, K, Ca, Mg, Na (Mehlich 3 extraction with acetic and nitric acids).

[0469] Description of the test samples and their soil exposure period.

[0470]

[0471] result

[0472] Macro visual appearance:

[0473] After 6 months of soil exposure, PLA without fillers looked the same as before soil exposure, indicating that soil exposure did not affect the test strips made from pure PLA. The PLA / blood and bone, PLA / fish meal, PLA / feather meal, and PLA / canola meal composites appeared structurally sound but showed granular discoloration from 2 months of soil exposure. This may indicate that fillers near the surface began to degrade, but PLA was more able to withstand it. In addition, there were some large cracks visible in the PLA / fish meal test strips. This indicates that the composites became increasingly brittle over time.

[0474] The test strips in which PLA was mixed with PBAT, PCL or PBS (and filler) appeared to be more corroded after 6 months than the test strips made of only PLA and filler. From 2 months of exposure, black and red areas were visible for the PBAT and PCL composites, and large brighter areas were visible for the PBS composites. The PHBV composite did not show such discoloration and appeared quite intact after 6 months of soil exposure.

[0475] Increasing the amount of blood and bone filler in the PBS / PLA test strips from 5% to 20% resulted in a more severely corroded appearance.

[0476] Microscopy:

[0477] Samples were prepared for scanning electron microscopy (SEM) imaging and examined at low and medium magnification to assess the gross structure and look for evidence of degradation in the soil exposed samples. The results are summarized in the table below.

[0478]

[0479]

[0480] After 4 to 6 months of soil exposure, the samples showed signs of deterioration in the form of cracks, cavities or small holes. In general, it was difficult to distinguish whether only the filler at the surface was degrading or whether the polymer was also degrading.

[0481] The surface of the PLA test strip without any filler remained as smooth after 6 months of soil exposure as it was before soil exposure.

[0482] In contrast, the test strips with PLA and 10% blood and bone fillers showed large surface cracks after 6 months of soil exposure. PLA with rapeseed meal filler showed large surface cracks and cavities, indicating severe degradation. PLA with feather meal filler also showed cracks, indicating some degradation. PLA with fish meal filler showed some cracks, but less than PLA with other fillers.

[0483] The PBAT / PLA composite material with blood and bone fillers shows that after 3 months of soil exposure, microorganisms colonize in blood and bones exposed to the surface. Also after 6 months, there are obvious surface cracks and cavities, but the overall surface is smooth, with small holes and cavities. After 6 months of soil exposure, the PHBV / PLA composite material with blood and bone shows a rougher surface with cavities and cracks. The PBS / PLA with blood and bone fillers and the PBS / PLA composite material with feather powder show a weathered surface with cracks and cavities. For the PCL / PLA with blood and bone fillers, the most severely degraded surface is observed.

[0484] In general, the presence of fillers near the surface tends to accelerate pitting and cracking of the composite surface after soil exposure.

[0485] In these cracks and holes, microorganisms can be seen. Microorganisms may also be present on flat surfaces, but they have been washed / brushed off when the samples were removed from the soil. Pure PLA samples with fillers tend to show more straight cracks compared to polymer / PLA composite samples, which show more holes and a rougher surface. The straight cracks in pure PLA samples with fillers may be caused by mechanical forces after the filler near the surface starts to biodegrade.

[0486] Microbial biodegradation was less likely to produce straight cracks in pure PLA sample materials with fillers. PHBV / PLA and PCL / PLA with blood and bone fillers were the most deteriorated composite samples.

[0487] After 6 months of soil exposure, a significant increase in surface degradation was observed compared to shorter exposure times.

[0488] Mass balance

[0489] The PLA composites with fillers showed only minor changes in the mass of the test strips after soil exposure, and in some cases an increase in mass, which may be due to the absorption of small amounts of water into the test strips during the soil exposure period.

[0490] The PBS / PLA composites with 10% or more blood and bone fillers and the PCL / PLA composites with blood and bone fillers achieved more than 2% mass loss after 4 or 6 months of soil exposure.

[0491] Total C, N, P, K and C:N ratio

[0492] Total Nitrogen (N) was determined using a furnace at extremely high temperatures. Total Phosphorus (P) and Total Potassium (K) were analyzed by a digestion method that dissolved the entire sample prior to quantifying these nutrients - the results of which are shown in the table below.

[0493] The carbon concentrations of the various composites ranged from 48.2% to 55.9% and were somewhat affected by the polymer type. The PCL / PLA composite contained the highest carbon concentration, while pure PLA polymer itself showed the lowest carbon concentration. The highest nitrogen concentrations were found in feather meal and 20% blood and bone fillers, while the highest phosphorus concentrations were found in blood and bone fillers, and the highest potassium concentrations were found in rapeseed meal fillers.

[0494] Prior to soil exposure, N concentrations ranged from almost nothing (500 ppm) (pure PLA with no fillers) to 13,000 ppm N (composites with PBS / PLA and 20% blood and bone), depending on the specific composite made.

[0495] After soil exposure, the nitrogen and potassium concentrations of PLA with various fillers decreased over time. The polymer / PLA composites with fillers also decreased after 6 months of soil exposure.

[0496] Because C concentrations are much more stable than N concentrations over time, the C to N ratios for most samples increased over time. The increased C to N ratios indicate that blood and bone and other fillers have become slightly more accessible to microbial communities and that they have begun to metabolize the fillers.

[0497] Overall, the concentrations of carbon and phosphorus were not affected by soil exposure time, while the concentrations of nitrogen and potassium decreased over time. This suggests that the filler did begin to biodegrade somewhat after soil exposure. The changes in carbon and phosphorus concentrations were probably too small to see any significant decreases. Carbon concentrations are usually very large, so only large changes are visible, while microorganisms generally require much less phosphorus than nitrogen for normal growth.

[0498]

[0499]

[0500] Extractable nutrients

[0501] Extractable nutrients were analyzed because any increase over time would indicate the availability of these nutrients once the composites were exposed to the soil. Extractable nitrogen was measured as extractable ammonium nitrogen, while extractable phosphorus (P), calcium (Ca), magnesium (Mg), potassium (K), and sodium (Na) were analyzed using Mehlich extraction. The Mehlich 3 extraction process is most commonly used to determine the availability of soil macronutrients (P, Ca, Mg, and K). This Mehlich extraction uses acetic acid and nitric acid during the extraction process.

[0502] The concentrations of extractable ammonium, phosphorus, potassium, sodium, calcium, and magnesium in the pure PLA samples were below the detection limit before soil exposure and after 6 months of soil exposure. This was expected because these pure PLA samples contained very low concentrations of total nitrogen, total phosphorus, and total potassium.

[0503] Before soil exposure, the most extractable ammonium, phosphorus, potassium, sodium, calcium, and magnesium were found in the PBS / PLA composite with 20% blood and bone filler, followed by the PBS / PLA composite with 15% blood and bone filler. The PBS / PLA composites with 5% and 10% blood and bone filler had much lower extractable nutrient concentrations, indicating that the extractable nutrients were derived from the filler. For the 10% filler formulation, before soil exposure, the most extractable ammonium was found in the PCL / PLA / blood and bone composite, while the most extractable phosphorus was found in the PLA / blood and bone composite, the most extractable sodium was found in the PLA / fish meal composite, the most extractable potassium and magnesium were found in the PLA / canola meal composite, and the most extractable calcium was found in the PHBV / PLA / blood and bone composite.

[0504] For most composites, extractable ammonium, phosphorus, calcium, and magnesium generally increased over time, whereas extractable sodium and potassium decreased, after 6 months of soil exposure (Table 12).

[0505] This suggests that as soils become exposed, more fill is exposed through material breakdown and nutrients become readily extractable.

[0506] The fact that more nutrients were extractable after soil exposure than before suggests that some material had already started to break down after soil exposure. There was not much difference between 3- and 6-month exposures, suggesting that extraction was limited to the exposed surface area.

[0507]

[0508]

[0509] Conclusions of Biodegradation Study 4

[0510] In general, PLA combined with PCL, PHBV or PBS polymers and 10% blood and bone filler or 10% feather meal filler began to biodegrade during the 6-month soil exposure period. Pure PLA / filler composites showed only physical degradation in the form of cracking and may show some degradation of the filler exposed on the surface. Increasing the blood and bone filler ratio in the PBS / PLA test strips from 5% to 20% did result in more severe degradation of the composites during soil exposure.

[0511] statement

[0512] Purely to avoid self-conflict with any previously filed disclosure and / or made or foreshadowed claims, applicants provide the following express statement. This statement should not be considered (unsuitably) representative of the generality of the invention described herein.

[0513] In some embodiments, the present invention may not include:

[0514] A composition comprising, for example, PBS:blood and bone in a ratio of 90:10; and / or

[0515] A composition comprising PBS:PLA:blood and bone in a ratio such as 60:30:10 and / or 75:15:10 and / or 45:45:10 and / or 30:60:10; and / or

[0516] A composition comprising, for example, PBS:PLA:sheep fecal pellets in a ratio of 60:30:10; and / or

[0517] Compositions comprising PBS:PLA:starch in ratios such as 60:30:10 and / or 45:45:10; and / or

[0518] A composition comprising, for example, PBS:PLA:kiwifruit "hair" in a ratio of 60:30:10; and / or

[0519] A composition comprising, for example, PBS:PLA:sanding machine dust in a ratio of 60:30:10; and / or

[0520] A composition comprising, for example, PBS:PLA:fishmeal in a ratio of 45:45:10; and / or

[0521] Plant containers and / or nursery pots and / or (plant) trays made from any of the compositions provided above; and / or

[0522] using fillers selected from the group consisting of: blood and bone; starch; sheep dung pellets; kiwifruit "hair"; sander dust; fertilizer; fish meal; soil conditioner; soil enhancer; weed suppressant; processed organic matter; processed animal matter (such as from terrestrial or marine species); and / or processed biological matter obtained from animals (such as including animal carcasses); and / or

[0523] using between 0.01-15% w / w of the composition as filler, such as between 1-15%, such as between 5-15%, such as at least 10% w / w; and / or

[0524] Using a single filler in the composition; and / or

[0525] Using polybutylene succinate (PBS), polylactic acid (PLA), polyhydroxyalkanoate (PHA), polyhydroxyalkanoate (PHB), poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) and / or combinations thereof; and / or

[0526] using PBS in an amount between 50-95% w / w of the composition, such as PBS in an amount between 60-90% w / w, such as PBS in an amount between 80-90% w / w of the composition; and / or

[0527] • A blend of PBS and PLA, such as in a ratio of about 3:1 to 1:1, such as 2.5:1 to 1.5:1, such as 2:1.

[0528] Unless the context clearly requires otherwise, throughout the specification and claims, the words “comprise,” “comprising,” etc. are to be interpreted in an inclusive sense, and not in an exclusive or exhaustive sense, that is, in the sense of “including but not limited to.” In contrast, the terms “consist,” “consisting of,” etc. are to be interpreted in an exclusive or exhaustive sense, that is, in the sense of “limited to.”

[0529] The entire disclosures of all applications, patents, and publications cited above and below, if any, are incorporated herein by reference.

[0530] The reference to any prior art in this specification is not and should not be taken as an acknowledgment or any form of suggestion that the prior art forms part of the common general knowledge in the field of endeavour in any country in the world.

[0531] The present invention may also be broadly said to include parts, elements and features mentioned or indicated individually or collectively in the description of the present application, including any or all combinations of two or more of the parts, elements or features.

[0532] Where in the above description integers or components are mentioned that have known equivalents thereto, then those integers are incorporated herein as if individually set forth.

[0533] It should be noted that various changes and modifications to the presently preferred embodiments described herein will be apparent to those skilled in the art. Such changes and modifications may be made without departing from the spirit and scope of the present invention and without diminishing the attendant advantages thereof. Therefore, it is intended that such changes and modifications be included in the present invention.

Claims

1. A biodegradable composition comprising a polymer and a filler such that the composition has a C:N ratio of 15 to 200.

2. The biodegradable composition according to claim 1, wherein Said C:N ratio of 15 to 200 is provided prior to exposure to composting conditions.

3. A biodegradable composition comprising a polymer and a filler such that the composition has an extractable phosphorus concentration of at least 5 mg / kg.

4. The biodegradable composition according to claim 3, wherein: The extractable phosphorus concentration of at least 5 mg / kg is provided prior to exposure to composting conditions.

5. A biodegradable composition comprising a polymer and a filler such that the composition has an extractable potassium concentration of at least 10 mg / kg.

6. A biodegradable composition comprising a polymer and a filler, such that the composition has: · C:N ratio of 15 to 200; and An extractable phosphorus concentration of at least 5 mg / kg; and / or Extractable potassium concentration of at least 10 mg / kg.

7. A biodegradable composition comprising a polymer and a filler, such that the composition has: · C:N ratio of 15 to 200; and An extractable phosphorus concentration of at least 5 mg / kg; and Extractable potassium concentration of at least 10 mg / kg.

8. A biodegradable composition comprising a polymer and a filler, such that the composition has: An extractable calcium concentration of at least 15 mg / kg; and / or An extractable magnesium concentration of at least 1 mg / kg; and / or An extractable sodium concentration of at least 15 mg / kg; and / or An extractable manganese concentration of at least 0.05 mg / kg; and / or An extractable iron concentration of at least 0.05 mg / kg; and / or An extractable aluminium concentration of at least 0.05 mg / kg; and / or An extractable zinc concentration of at least 0.05 mg / kg; and / or An extractable copper concentration of at least 0.1 mg / kg; and / or · Extractable boron concentration of at least 0.1 mg / kg.

9. A biodegradable composition comprising a polymer and a filler, such that the composition has: · C:N ratio of 15 to 200; and An extractable phosphorus concentration of at least 5 mg / kg; and / or An extractable potassium concentration of at least 10 mg / kg; and / or An extractable calcium concentration of at least 15 mg / kg; and / or An extractable magnesium concentration of at least 1 mg / kg; and / or An extractable sodium concentration of at least 15 mg / kg; and / or An extractable manganese concentration of at least 0.05 mg / kg; and / or An extractable iron concentration of at least 0.05 mg / kg; and / or An extractable aluminium concentration of at least 0.05 mg / kg; and / or An extractable zinc concentration of at least 0.05 mg / kg; and / or An extractable copper concentration of at least 0.1 mg / kg; and / or · Extractable boron concentration of at least 0.1 mg / kg.

10. The biodegradable composition according to any one of claims 1 to 9, wherein: The composition comprises: PLA; PBS and PLA; PBAT and PLA; PHBV and PLA; or PCL and PLA.

11. The biodegradable composition according to any one of claims 1 to 10, wherein: When present, PHB is used in combination with a polymer selected from the group consisting of: PLA; PBS; PBAT; PHBV; and PCL.

12. The biodegradable composition according to claim 11, wherein When present, PHB is used as a minor component in combination with a polymer selected from the group consisting of: PLA; PBS; PBAT; PHBV; and PCL.

13. The biodegradable composition according to any one of claims 1 to 10, wherein: The composition does not include PHB.

14. A filler for incorporation into a biodegradable composition, the filler providing a source of at least one of: nitrogen; phosphorus; potassium; calcium; magnesium; sodium; manganese; iron; aluminum; zinc; copper; and boron, such that the biodegradable composition incorporating the filler has: A C:N ratio of 15 to 200; and / or An extractable phosphorus concentration of at least 5 mg / kg; and / or An extractable potassium concentration of at least 10 mg / kg; and / or An extractable calcium concentration of at least 15 mg / kg; and / or An extractable magnesium concentration of at least 1 mg / kg; and / or An extractable sodium concentration of at least 15 mg / kg; and / or An extractable manganese concentration of at least 0.05 mg / kg; and / or An extractable iron concentration of at least 0.05 mg / kg; and / or An extractable aluminium concentration of at least 0.05 mg / kg; and / or An extractable zinc concentration of at least 0.05 mg / kg; and / or An extractable copper concentration of at least 0.1 mg / kg; and / or · Extractable boron concentration of at least 0.1 mg / kg.

15. A method for increasing the biodegradation rate of a composition, comprising mixing a filler and a polymer so that the composition has: A C:N ratio of 15 to 200; and / or An extractable phosphorus concentration of at least 5 mg / kg; and / or An extractable potassium concentration of at least 10 mg / kg; and / or An extractable calcium concentration of at least 15 mg / kg; and / or An extractable magnesium concentration of at least 1 mg / kg; and / or An extractable sodium concentration of at least 15 mg / kg; and / or An extractable manganese concentration of at least 0.05 mg / kg; and / or An extractable iron concentration of at least 0.05 mg / kg; and / or An extractable aluminium concentration of at least 0.05 mg / kg; and / or An extractable zinc concentration of at least 0.05 mg / kg; and / or An extractable copper concentration of at least 0.1 mg / kg; and / or · Extractable boron concentration of at least 0.1 mg / kg.

Citation Information

Cited By

  • Preparation method of polyvinyl biodegradable composite mulching film

    CN120191016A